Revealing the biocontrol potential of endophytic bacteria isolated from wild soybean seeds against soybean gray leaf spot - Xiaoqing Yi; Mengyu Sun; Sixiang Wang; Qing Qu; Yue Zhao; Yuzhu Dong; Xuemei Li; Lanlan Wang; Chenxi Wang; Ruowen Mei; Cuimei Yu; Ze Wang; et al. (Physiological and Molecular Plant Pathology, 2026)

Valorizing lignocellulosic biomass-derived hydrothermal carbonization aqueous phase for heavy metal removal from contaminated soil: Molecular composition-mediated metal-specific complexation - Mei Huang; Yangchun Li; Yangziyun Zhang; Zhi Liao; Li Zhao; Dong Tian; Yan Liu; Yongjia Lei; Yu Zhao; Shuanglin Chen; Fei Shen (Bioresource Technology, 2026)

Molecularly imprinted electrochemical detection of inositol trispyrophosphate in sweat as an emerging oxygen-transfer doping agent - Zehang You; Yang Li; Hanfei Liu; Chen Chen; Tao Mei; Quan Wang; Yifan Dong; Yuanhua Shao (Analytica Chimica Acta, 2026)

Bench-scale proof-of-concept evaluation of whole-cell quorum quenching for fouling mitigation in a constant-flux membrane bioreactor. - Jiale Han; Xiaohui Chen; Xiaoyu Wang; Zimiao Yan; Xinjiao Dong; Yaru Li; Chenjie Mei; Shimei Ge (Journal of Water Process Engineering, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Pt clusters encapsulated in ZSM-5 channel for effective dehydrogenation of long-chain alkane - Shanhui Zhu; Jiamin Yuan; Zhiqiang Liu; Shiying Li; Qi Li; Mei Dong; Weibin Fan (Chemical Engineering Journal, 2026)

Spatial distribution and compositional profile of microplastics in oil and gas extraction solid wastes: An overlooked source of microplastics - Yongxu Jin; Jianqi Dai; Xiang Wang; Shan Zhong; Yingzhou Huang; Xudong Mei; Shijie Wang; Min Hao; Jinwei Fang; Yunmin Zeng; Dong Li (Chemical Engineering Journal, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

First Report of Powdery Mildew Caused by Podosphaera xanthii on Sphagneticola × guangdongensis in Guangdong Province, China - Mei-Li Zhao; Yu-Xin Zhang; Zhen Qiao; Dong-Hui Huo; Dan Wang (Crop Protection, 2026)

Structurally diverse diterpenoids from Euphorbia milii: Discovery and RORγt-binding evaluation - Meng-Yuan Dai; Xue-Li Hu; Wen-Chang Li; Zhi Lu; Bin-Yuan Jiang; Hua-Mei Chen; Ying Zeng; Dong-Hua Cao (Phytochemistry, 2026)

Establishment of a new germ-free Spodoptera frugiperda model to explore the gut microbiota on larval, pupal development and adult reproduction - Bin Li; Hai-Dong Sun; Mei Liu; Xin He; Xiao-Long Liu; Min Lu (Journal of Insect Physiology, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Cardio-Oncology in Cold Climates: Epidemiological Features, Bidirectional Interaction Mechanisms, and Integrated Management Strategies - Yuexin Li; Yifei Zhang; Haobo Sun; Ying He; Dongqing Gao; Tingting Ding; Xuemei Chen; Zhonghua Sun; Shuai Jiang; Mei Dong (Cardiovascular Toxicology, 2026)

Coordinated cross-system recovery framework for large-scale metro stations under extreme flooding - Hai-Yun Li; Huan-Feng Duan; Dong-Mei Zhang; Xu-Wei Zhao (Tunnelling and Underground Space Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

GNPS-guided discovery of antifungal brominated metabolites from Chaetomium elatum FH-3 via NaBr-regulation and biotransformation - Jing-jing Su; Yin-han Teng; Bai-xue Yin; Hai-fang Wang; Yu-ze Li; Wei Wang; Xiao-mei Song; Dong-dong Zhang; Hao Fan (Phytochemistry Letters, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Thermal comfort of medical staff in operating rooms: a review and future perspectives - Hao-Yi Zhao; Xiao-Dong Jian; Bin Zhou; Wen-Jie Li; Zhi-Hang Xu; Mei-Lan Tan; Xiang Zhang (Energy and Buildings, 2026)

Putty–clay perspective on asset stickiness and stranding in China's energy transition: Quantitative assessment using a hybrid support vector regression–system dynamics model - Jianyuan Li; Mei Sun; Xiucheng Dong (Energy Policy, 2026)

PIP4K2A Attenuates Cerebral Ischemia/Reperfusion Injury by Reducing the TRIB3-p62 Complex Burden and Modulating AKT/mTOR Signaling - Bodun Ma; Xiaotian Yu; Mei Li; Hao Zhu; Xiaofeng Dong; Shuai Yu; Meixia Wang; Guanhui Wu; Xiao Wang; Ruiyao Hu; Hongxuan Feng (Translational Stroke Research, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

EasyAphid: a comprehensive method for aphid infestation quantification in wheat using EVC-YOLO-Seg model and RGB images - Haotian Deng; Hui Deng; Jiawei Chen; Xin Liu; Zijun Pei; Chenzhao Gao; Qi Sun; Xin Zhang; Shijie Zhai; Xueli Hu; Shuming Fan; Xiao Wang; et al. (Computers and Electronics in Agriculture, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Chitosan/graphene oxide composite aerogel based on bionic-design of morning glories for artificial sweetener remediation: Exploring novel adsorption mechanisms and sustainable applications - You-Ya Sun; Wen Li; Mei Li; Yao-Yang Sun; Hai-Qin Lu; Yan-Shu Xiong; Hao Dong (Food Chemistry, 2026)

A novel C17-sesquiterpene alkaloid derived from Dendrobium huoshanense : in vitro evaluation of its anti-lung cancer activity and molecular dynamics simulation study - Jun Chen; Xiu-Mei Li; Yong-Peng Sun; Ya-Feng Dai; Shi-Hao Li; Nai-Fu Chen; Nai-Dong Chen (Natural Product Research, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Metabolite profiling of organophosphate ester exposure and type 2 diabetes mellitus risk: A metabolomics study in an epidemiological setting - Qian Zou; Qinghua Zhang; Mei Liu; Honghua Li; Shiheng Luo; Xiaodong Li; Gaofeng Zhang; Xiaoya Wu; Zidi Gao; Guibin Jiang; Yin Dong (Journal of Hazardous Materials, 2026)

Hydrophobic deep eutectic solvents for highly efficient n-hexane capture - Yan Zhao; Yanlong Xu; Anna Mei; Yingzhe Chen; Chee Sien Wong; Zhao Huang; Yulong Shan; Jianmeng Chen; Qian Li; Dong-Zhi Chen (Journal of Environmental Sciences, 2026)

Construction of PtIn@S-1 || hollow H-ZSM-5 composite catalyst for propane aromatization - Zhao Ma; Sen Wang; Shiying Li; Zhikai Li; Han Wang; Qi Li; Baichao Li; Dezhi Shi; Pengfei Wang; Mei Dong; Weibin Fan (Fuel, 2026)

The physicochemical and simulated digestive characteristics of yam flours processed by different thermal processing methods - Ya Huang; Mei Deng; Xuchao Jia; Lihong Dong; Fei Huang; Qin Ma; Mingwei Zhang; Shan Liang; Yanxia Chen; Fengjuan Li; Ruifen Zhang (Food Chemistry, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Synergistic engineering of a MYB transcription factor boosts fucoxanthin and biomass co-production in the diatom Phaeodactylum tricornutum - Ting-Bin Hao; Mei-Qi Li; Rongxiang Guo; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Algal Research, 2026)

Cross-system modeling and analysis of cascading failure propagation in large-scale metro stations under extreme flooding events - Hai-Yun Li; Dong-Mei Zhang; Huan-Feng Duan; Xu-Wei Zhao (Tunnelling and Underground Space Technology, 2026)

PM2.5-induced ferroptosis via the miR-188-3p/GPX4 axis disrupts renal erythropoietin production - Wenqi Chen; Shanshan Chen; Lirong Bai; Mei Zhang; Chuan Dong; Li Fan; Qi Zan; Ruijin Li (Toxicology and Applied Pharmacology, 2026)

A coupled B-C-H-W model for predicting wave-induced residual liquefaction of bio-grouted seabed around buried tunnels - Yujie Li; Changrui Dong; Sen Mei; Beifeng Lv; Xingye Sun; Peng Zhu (Ocean Engineering, 2026)

Speciation-dependent bioaccessibility of lead in e-waste dismantling soils: Synchrotron spectroscopy reveals molecular controls across physiological compartments - Jian Liu; Yi-Fan Li; Yi-Heng Wang; Dong-Xing Guan; Hao-Ran Guan; Yi-Ren Li; Xing-Mei Liu (Journal of Hazardous Materials, 2026)

Rapid identification and prediction of the botanical origins and main components of Chinese yam based on a multimodal data fusion of near-infrared spectra and visualization image information - Xue-Qing Fan; Ming-Hui Wei; Li Yang; Mei Xue; Chun-Juan Pu; Jian-Mei Yin; Xi-Chen Yang; Pei-Dong Chen; Gui-Sheng Zhou; Tian-Shu Wang; Hui Yan (Food Chemistry, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Three phloridzin derivatives capable of anti-oxidant from Malus toringoides (Rehd) Hughes - Li Liu; Wei-wei Tian; Ying-chao Wang; Can Ren; Dong-mei Yu; Jian-bo Wang; Jun-ning Zhao; Hua Hua (Natural Product Research, 2026)

Integrated nanoarchitectonics of porous carbon with high specific surface area and liquid fertilizer from distiller's grains by hydrothermal process - Yao Zhao; Zhanglin Liu; Binglin Wang; Jinguang Hu; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Jianmei Zou; Fei Shen (Biomass and Bioenergy, 2026)

Monte-Carlo-assisted endo-exo temporal transformer for high-confidence interval forecasting of daily runoff - Xiao-xue Hu; Dong-mei Xu; Wen-chuan Wang; Jun Wang; Zong Li (Stochastic Environmental Research and Risk Assessment, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Artemisia argyi essential oil - loaded β-cyclodextrin/whey protein microcapsules: dual antifungal and disease resistance-inducing effects to enhance blueberry shelf life - Yue-yan Chen; Ning-ying Zhu; Wei Gao; Yu Wang; Mei-qing Li; Dong-liang Wang; Xue-ling Gao; Jin Liang; Hai-wei Zhang (Food Chemistry, 2026)

Mitophagy Inhibition Suppresses Seizures in Status Epilepticus Mice by Decreasing Hippocampal NLRC4 Expression - Zhi-Cheng Dong; Min Liu; Jin-Yi Zhou; Li-Qun Geng; Mei Li; Xu-Qin Chen (Journal of Molecular Neuroscience, 2026)

A multi-layer coupling framework for hydrodynamic simulation of underground station flooding - Dong-Mei Zhang; Hai-Yun Li; Wen-Ding Zhou; Si-Rui Chen; Zhong-Kai Huang (Tunnelling and Underground Space Technology, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

Petrogenesis and magmatic-hydrothermal evolution of the Dahongliutan pegmatite-type lithium deposit, Western Kunlun, NW China: A tourmaline perspective - Yong-Qi Xia; Ming-Jie Tuo; Nuerkanati Madayipu; Jianatiguli Wusiman; Dong-Mei Qi; Nuo Li (Lithos, 2026)

The secreted in xylem protein Foc4-SIX13 of Fusarium oxysporum f. sp. cubense race 4 targets the banana Nudix hydrolase and contributes to its virulence - Wenjing Chen; Jiamin Zheng; Jiahui Wu; Rujing Zeng; Zheng Li; Yinghua Huang; Tom Hsiang; Handa Song; Mei Luo; Zhangyong Dong (Fungal Biology, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Hierarchical Framework for Reservoir Co-management: A Cross-scale Reservoir Dispatch Paradigm Balancing Energy and Morphogenic Flow Needs - Hong Zeng; Tian-Yao Zhang; Yi-Ming Liao; Guang-Wen Ma; Ji-Dong Li; Wei-Bin Huang; Yan-Mei Zhu; Shi-Jun Chen (Water Resources Management, 2026)

Aflatoxin B1 interferes with lncRNA-mRNA network to inhibit proliferation of bovine endometrial epithelial cells - Yin-Yin Li; Yue Bai; Yu-Mei Chen Yan; Pei-Yu Dong; Min Zhang; Xi-Feng Zhang; Yan-Ni Feng (Mycotoxin Research, 2026)

Study on the effect and mechanism of Fenton-like reaction based on UV/H2O2 to degrade sulfamethoxazole in water - Baochang Zhou; Guifang Li; Zhangbin Pan; Bin Dong; Zhenqi Du; Baiqiang Zhang; Mei Li; Yonglei Wang; Ruibao Jia (Environmental Science and Pollution Research, 2026)

Research progress on triterpenoids in the genus Rubus : a comprehensive review - Xi-Ya Li; Ting-Cai Dong; Yong-Fan Zi; Yan Luo; Yuan Li; Rui-Feng Mei; Le Cai (Natural Product Research, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

miR-23a modulates chlorantraniliprole susceptibility by targeting SfGSTs3 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Yong-Po Lv; Bai-Zhong Zhang; Meng-Yuan Zhang; Ling-Ling Cui; Ren-Jie Li; Dong-Mei Chen; Yu-Yang Peng; Run-Qiang Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Reactive interfacial oxygen vacancies in Ru/TiO2 for efficient reductive amination of bio-based carbonyl compounds - Shanhui Zhu; Ruiqi Wu; Xiaoming Li; Mei Dong; Weibin Fan (Chemical Engineering Journal, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

A new polyketide from Penicillium sp. HK-G2 and its inhibitory activity against α-glucosidase - Jie Zhen Shi; Yan-Li Zhang; Jin Hua Yu; Da-Mei Wang; Dong Gan; Zhong-Tao Ding (Natural Product Research, 2025)

Long-term settlement prediction of shield tunnel interval considering spatial information - Dong-Mei Zhang; Zhao-Geng Chen; Yi-Ming Shen; Zhong-Kai Huang; Xiao-Chuang Xie; Xiao-Yang Guo; Deng-Fei Yan; Yong-Bo Li (Tunnelling and Underground Space Technology, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Longitudinal seismic response characteristics of shield tunnel structures in liquefiable soils - Yiyao Shen; M. Hesham El Naggar; Dong-Mei Zhang; Liyun Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Reed silicon accumulation indirectly regulates nitrogen metabolism in response to rise in groundwater depth by improving water use efficiency in the desert oasis area of Northwest China - Jian-Jun Kang; Wen-Zhi Zhao; Zhi-Bin He; Bing Liu; Dong-Mei Zhang; Li-Wen Zhao; Xu HP (Plant and Soil, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

First pathogenic non-coding variant in MMACHC: a functional deletion in the 5′-UTR associated with cobalamin C deficiency - Ying Zhang; Leyi Wang; Xiangyu Liu; Mei Sun; Hong Wang; Jiaci Li; Shuyue Zhang; Ning Zhang; Dong Li; Jianbo Shu; Chunquan Cai (Molecular Biology Reports, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Establishment of an event-specific quantitative real-time PCR method for genetically modified maize LD05 with combined insect resistance and herbicide tolerance - Wenlan Li; Wujun Jin; Mei Dong; Xinwei Hou; Zhaohua Ding; Zhaodong Meng; Runqing Yue (Journal of Consumer Protection and Food Safety, 2025)

Inhibitory Effect of TrxR Inhibitor Ag (Ⅰ) Schiff Base Complex Against Cervical Cancer Via ROS-mediated ASK1/MAPK Signaling and Autophagy - Jian-Jun Liu; Jia-Hua Zou; Bin Dong; Xue-Ping Lu; Li-Feng Chen; San-Mei Ma; Zhong Liu (Biological Trace Element Research, 2025)

High-throughput wheat seedling phenotyping via UAV-based semantic segmentation and ground sample distance driven pixel-to-area mapping - Honghao Zhou; Qing Li; Bingxi Qin; Haijiang Min; Shaowei Liang; Xiao Wang; Jian Cai; Qin Zhou; Mei Huang; Dong Jiang; Yingxin Zhong; Jiawei Chen (Computers and Electronics in Agriculture, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Development of a rapid method for the determination of the spatial distribution of protein in wheat grain using mature resin section and image processing algorithm - Hengtong Wang; Haijiang Min; Minghao Gao; Han Zhong; Chuan Zhong; Zenan Ban; Qin Zhou; Xiao Wang; Jian Cai; Qing Li; Mei Huang; Dong Jiang; et al. (Journal of Cereal Science, 2025)

Failure mechanism of rock tunnels subjected to combined reversed fault dislocation and subsequent seismic excitation - Dong-Mei Zhang; Li Guo; Zhong-Kai Huang; Yi-Yao Shen; Kyriazis Pitilakis (Computers and Geotechnics, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

Effect of rubber-tracked chassis roller on soil surface vertical stress distribution based on finite element method - Zhuohuai Guan; Haitong Li; Tao Jiang; Licheng Xing; Min Zhang; Dong Jiang; Mei Jin (Journal of Terramechanics, 2025)

Dual-sulfur defects decorated 1T-WS2/Cd0.5Zn0.5S heterojunctions for boosted photocatalytic hydrogen evolution - Mei Dong; Wenjun Li; Liang Geng; Ruixue Huang; Hongli Han; Yuan Liu (Journal of Environmental Chemical Engineering, 2025)

The role of potassium in lode gold mineralization: insights from ab initio molecular dynamics and geochemical modeling - Gao-Hua Fan; Jian-Wei Li; Yuan Mei; Si-Yu Hu; Ri-Chen Zhong; Chang Yu; Xiao-Dong Deng; Hao Cui; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Study on a novel Zn-containing HZSM-5 catalyst for ethylene aromatization - Baichao Li; Jiabei Shao; Shiying Li; Qi Li; Pengcheng Feng; Zhangfeng Qin; Jianguo Wang; Weibin Fan; Mei Dong (Fuel, 2025)

A 3D point cloud and deep learning based automated process for quantifying multi-scale phenotypes in sliced bread - Honghao Zhou; Jungao Zhang; Qin Zhou; Xinru Wang; Haijiang Min; Bingxi Qin; Shaowei Liang; Xiao Wang; Yingxin Zhong; Jian Cai; Mei Huang; Qing Li; et al. (Food Research International, 2025)

Effect of cold plasma modification on bacterial cellulose and its dispersion behavior in chitosan-based matrix - Hui-mei Liu; Yao-yao Wang; Xiangzhen Ge; Yun Chen; Xi-guang Ye; Yong Hu; Mengfan Li; Chao Huang; Dong-mei Li (Food Bioscience, 2025)

Impact of per- and polyfluoroalkyl substances exposure on renal dysfunction: Integrating epidemiological evidence with mechanistic insights - Weitao Su; Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Zhiqiang Dong; Ming Yang; Jingtao Wu; Huicai Guo; Ang Li (Environmental Pollution, 2025)

Ionic liquid-enhanced Nafion-based ionic polymer sensors: Impact of immersion temperature and imidazolium types - Gangqiang Tang; Mingfei Jiang; Xin Zhao; Zhuoao Du; Dong Mei; Chun Zhao; Lijie Li; Yanjie Wang (Chemical Engineering Journal, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Unlocking the power of sesquiterpenoids: phytochemistry and bioactivities in Artemisia (2017–2023) - Li Ping Tang; Tao Liu; Xiao Yu Han; Bin Li; Hong Dong Liu; Xue Mei Gao (Phytochemistry Reviews, 2025)

Effects of AMPEP (Ascophyllum marine plant extract powder) and SJEP (enzymatic extracts of Saccharina japonica) on growth and resistance of red macroalga Pyropia yezoensis - Guo-Ying Du; Li-Hong Ma; Yu-Qing Wang; Xin-Yu Zhang; Yan-Jun Gong; Dong-Mei Wang (Algae, 2025)
Seaweed extracts are widely used as biostimulants in terrestrial crops but remain underexplored for economic macroalgae. This study investigated the effects of Ascophyllum marine plant extract powder (AMPEP) and Saccharina japonica extract powder (SJEP) on the growth and stress resistance of Pyropia yezoensis, a commercially significant red macroalga along the Northeast Asia coast. Through gradient analysis, optimal concentrations were determined to be 0.05 g L−1 for SJEP and 0.1 g L−1 for AMPEP, based on their effects on daily growth rate (DGR) and photosynthetic performance. Both extracts significantly improved resistance to red rot disease, reducing lesion area while increasing DGR, photosynthetic efficiency, and pigment content compared to the control. Additionally, SJEP and AMPEP elevated superoxide dismutase (SOD) activity and suppressed malondialdehyde (MDA) accumulation. Under cold stress, the extracts mitigated declines in DGR, photosynthetic parameters, pigment levels, and SOD activity, while restraining MDA elevation. Notably, the expression of cold-responsive genes (PyABCC1 and PyABCI1) peaked in SJEP treatment and remained elevated in AMPEP treatment, surpassing the control by several-fold. Overall, SJEP outperformed AMPEP, likely due to its higher polysaccharide and polyphenols. These results support brown algal extracts—particularly enzymatic extracts—as practical biostimulants to enhance growth, disease resistance, and cold tolerance in P. yezoensis cultivation.

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Artemsieverlides A–M, diverse sesquiterpenoid dimers with antihepatic fibrosis activity isolated from Artemisia sieversiana based on molecular networking - Wei Dong; Tian-Ze Li; Xiao-Yan Huang; Yan-Mei Weng; Chang-An Geng; Ji-Jun Chen (Phytochemistry, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Rational design of core-shell polyvinylpyrrolidone (PVP)-MIL-101(Fe)@CoZn-ZIF nanocomposites for peroxymonosulfate activation toward 4-nitrophenol degradation - Mei Dong; Qiguang Cao; Song Li; Kebin Li (Journal of Water Process Engineering, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Activation of molecular oxygen over MnOX/CeO2 for catalytic wet air oxidation of high-concentrated phenolic pollutants - Li Zhao; Haiping Mao; Yuanjing Lai; Jinsong He; Dong Tian; Mei Huang; Yongjia Lei; Fei Shen; Jianmei Zou (Journal of Environmental Management, 2025)

Sensory characteristics and key odor-active compounds of oxidized Antarctic krill oil: A comparative study with oxidized fish oil - Gui-Mei Dong; Rui-Ying Wang; Fa-Wen Yin; De-Yang Li; Lei Qin; Da-Yong Zhou (Food Chemistry, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Microbial pterins as potential indicators of organic carbon dynamics in estuarine and coastal sediments - Kang Mei; Yitong Pan; Danny Alejandro Osorio; Lizhe Cai; Hualong Hong; Mohammad Mazbah Uddin; Song Wang; Xin Xiao; Xuri Dong; Li Chen; Shicong Xiao; Deli Wang (CATENA, 2025)

Berberine dissociates mitochondrial complex I by SIRT3-dependent deacetylation of NDUFS1 to improve hepatocellular glucose and lipid metabolism - Xuekai Wang; Hu Li; Jianrui Li; Lei Lei; Jingchen Xu; Han Sun; Jiayu Li; Jing Jiang; Hongying Li; Mei Tang; Biao Dong; Yue Gong; et al. (Science China Life Sciences, 2025)

A novel TCN-augmented CNN-LSTM architecture for accurate monthly runoff forecasting - Dong-mei Xu; Qi-qi Zeng; Wen-chuan Wang; Miao Gu; Yi-yang Wang; Zong Li (Earth Science Informatics, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Screening speleothem U/Th ages through crystal petrography analysis: A case study from Rige cave in the Southeast Tibetan Plateau - Shihao Lei; Hanying Li; Youwei Li; Rui Zhang; Mei He; Xiyu Dong; Xiaowen Niu; Jian Wang; Haiwei Zhang; Zhengguo Shi; Youfeng Ning; Hai Cheng (Quaternary International, 2025)

Investigating the antifungal mechanism of Artemisia argyi essential oil against Botrytis cinerea, Alternaria alternata, and Penicillium digitatum and its application in extending blueberry shelf life - Yue-yan Chen; Yu-dong Zhang; Li Wang; Mei-qing Li; Yu Wang; Jin Liang; Dong-liang Wang; Hai-wei Zhang (International Journal of Food Microbiology, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Effect of Seismic Bedrock Interface Depth on Surface Ground Motion Parameters of Deep Overburden Sites - Yiyao Shen; Xiuli Du; Liyun Li; Dong-Mei Zhang (Journal of Earth Science, 2025)

Inhibitory effects of flavonoids and alkaloids from the traditional antihyperglycemic herb Polygonatum kingianum var. grandifolium on α-glucosidase activity - Qing-Dong Ma; Xu-Juan Fu; Xiao-Qin Xiong; Dong-Mei Liu; Zhuo-Jun Li; Wei Gong; Dong-Qin Guo; Dong-Yang Yi (Natural Product Research, 2025)

Ruthenium and nitrogen co-doped biochar for sulfamethoxazole degradation via peroxymonosulfate activation: Performance and mechanism - Lianghui Guo; Jiajun Xu; Dong Liu; Aoxiang Yin; Runyao Han; Guifan Gong; Shi Li; Zimeng Liu; Keke Zhi; Mei Wu (Process Safety and Environmental Protection, 2025)

Recycling paper packaging waste into Fe-biochar pellet catalyst for tetracycline degradation via peroxymonosulfate activation - Li Zhao; Kangting Du; Mei Huang; Dong Tian; Jinsong He; Yongjia Lei; Yan Liu; Guochun Lv; Jianmei Zou; Fei Shen (Environmental Research, 2025)

Cyclodextrin-based self-assembling hydrogel for Photothermal-controlled nitric oxide release in stage-specific treatment of MRSA-induced arthritis - Guowei Li; Xiaohua Wei; Kai Lv; Dongna Xie; Mei Liu; Yi Xu; Dong Ma; Genlong Jiao (Carbohydrate Polymers, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Effects of temperature and salinity on CO2 fluxes dynamics and respiration metabolism in the sea cucumber Apostichopus japonicus (Selenka) - Yaoping Mei; Yuling Xu; Qinfeng Gao; Zhao Li; Shuanglin Dong (Marine Pollution Bulletin, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

A novel, ridged enlarging lateral space drip irrigation pattern (ReDiP) for high- yield and WUE spring wheat in Xinjiang, China - Liulong Li; Zijian Wang; Wenliang Wan; Zhaofeng Li; Jian Cai; Qin Zhou; Mei Huang; Yingxin Zhong; Xiao Wang; Dong Jiang (Field Crops Research, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

TSPO activation ameliorates maternal immune activation induced PV interneuron deficits via BDNF/TrkB signaling - Ming-Jie Mao; Hui-Ling Yu; Qing-Zhen Liu; Ya-Zhou Wen; Ming Jiang; Hong-Mei Yuan; Hua-Bei Zeng; Li-Dong Zhang; Shan-Wu Feng (Psychopharmacology, 2025)

Advances in research on the control of pollen tube growth by calcium in higher plants - Yi Hua Lin; Mei Zhen Lin; Hui Qiao Tian; Dong Xiao Li (Plant Science, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

High-Performance Multi-Responsive actuators based on ionic Polymer-Graphene janus film for multimodal soft robots - Gangqiang Tang; Shilong Liu; Xiaofeng Yu; Dong Mei; Xin Zhao; Chun Zhao; Lijie Li; Yanjie Wang (Chemical Engineering Journal, 2025)

Fuzzy-based method for seismic soil structure interaction and performance evaluation of subway stations - Yiyao Shen; M. Hesham El Naggar; Dong-Mei Zhang; Liyun Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Two new compounds from Pentadesma butyracea and their biological activities - Yue Yang; Li Hua Gong; Fu Hua Peng; Tao Jiang; Jian Guo Hu; Hong Dong Liu; Bin Li; Yin Xia Yang; Jing Ying Peng; Xue Mei Gao (Phytochemistry Letters, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Two unprecedented 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones with anti-Helicobacter pylori activity from agarwood of Aquilaria sinensis 'Reke 1' - Ke-Xin Qin; Hao Wang; Li Yang; Yan-Mei Wei; Cai-Hong Cai; Hui-Qin Chen; Wen-Hua Dong; Wei Li; Xian-Yun Yan; Jun Zeng; Wen-Li Mei; Jie Jian; et al. (Phytochemistry Letters, 2025)

Effect of vertical load on track traction under different soil moisture content - Zhuohuai Guan; Dong Jiang; Min Zhang; Mei Jin; Haitong Li; Tao Jiang (Journal of Terramechanics, 2025)

Role of S(IV) in enhancing permanganate oxidation of emerging contaminants: pH dependence of reactive species generation - Chen-Yan Hu; Xin-Yu Yang; Li-Li Hu; Hao Liu; Jia-Nan Chen; Ling-Mei Gao; Zheng-Yu Dong (Journal of Environmental Chemical Engineering, 2025)

Structural controls on the magma emplacement and distribution of sulfide orebodies in the Kalatongke Cu-Ni sulfide district, NW China - Xue-Hai Wang; Ke-Zhang Qin; Xing-Wang Xu; Dong-Mei Tang; Ya-Jing Mao; Lei Zhang; Min-Qiang Zhang; Fang-Lin Yuan; Yi Li (Journal of Asian Earth Sciences, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Analysis of non-uniform force distribution characteristics among tendons of prestressed anchor cable and experimental study on equal stress tensioning - Wen-Hui Bian; Jun Yang; Ke-Xue Wang; Jia-Wang Zhan; Yi Fang; Mei-Qiang Dong; Zhe Li (Engineering Structures, 2025)

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Siegesoxylipin A‒J, previously undescribed phyto-oxylipins inhibition of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci from Sigesbeckia orientalis - Zhong-Shun Zhou; Wen-Biao Zu; Yan-Yan Zhu; Mei-Zhen Wei; Yue-Ming Jiang; Zhao-Jie Wang; Yun-Li Zhao; Xiao-Dong Luo (Phytochemistry, 2025)

Rational design of hierarchical porous structure of ZSM-22 for boosting high-efficiency selective hydrogenation of oleic acid to jet fuel - Zhentao Liu; Jinlin Mei; Xiaoyang Kong; Zikang Chen; Dong Li; Haidong Li; Chunya Wang; Yanjun Gong; Chunming Xu; Xilong Wang (Chemical Engineering Journal, 2025)

Combined effects of the visual-thermal environment on restorative benefits in hot outdoor public spaces: A case study in Shenzhen, China - Wen DONG; Donghui DAI; Mei LIU; Yaowu WANG; Shuang LI; Pengyuan SHEN (Building and Environment, 2025)

WaveTransTimesNet: an enhanced deep learning monthly runoff prediction model based on wavelet transform and transformer architecture - Dong-mei Xu; Zong Li; Wen-chuan Wang; Yang-hao Hong; Miao Gu; Xiao-xue Hu; Jun Wang (Stochastic Environmental Research and Risk Assessment, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Rapid oxidation of emerging contaminants by far-UVC/chlorine system: Energy efficiency and synergistic mechanism - Chen-Yan Hu; Li-Li Hu; Tian-Yang Zhang; Xin-Yu Yang; Hao Liu; Jia-Nan Chen; Ling-Mei Gao; Zheng-Yu Dong (Journal of Water Process Engineering, 2025)

Collaborative performance of enzymatic saccharification and organic pollutant degradation from PHP (phosphoric acid coupled with hydrogen peroxide) pretreatment of lignocellulose - Miao Lei; Xuan Dong; Mei Huang; Li Zhao; Jianmei Zou; Dong Tian; Yongjia Lei; Jinsong He; Fei Shen (Journal of Environmental Management, 2025)

Biosurfactants are green and versatile enhancers for sustainable treatment of oily sludge: A review - Feng Zhao; Qingfeng Cui; Han Su; Chunyan Li; Mei Dong (Journal of Environmental Chemical Engineering, 2025)

Molecular basis of E93-dependent tissue morphogenesis and histolysis during insect metamorphosis - Mei Zeng; Zi-Yu Yan; Ya-Nan Lv; Jia-Ming Zeng; Ning Ban; Dong-Wei Yuan; Sheng Li; Yun-Xia Luan; Yu Bai (Insect Biochemistry and Molecular Biology, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Microplastics release from infant feeding bottles and milk storage bags - Long Zhao; Yiying Gu; Hua Cai; Xin Xu; Jianguo Yu; Jing Li; Ying Shen; Leiyan Zhu; Yan Jin; Mei Zhang; Ruihua Dong; Bo Chen (Food Control, 2025)

Differential impact of wildfire and rice straw ash on the skin microbiota of Rana dybowskii adults and tadpoles - Xin-zhou Long; Ming-da Xu; Wen-jing Dong; Xiu-mei Yang; Li-yong Cui; Qing Tong (Environmental Pollution, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Synthesis, molecular docking studies of formononetin derivatives as potent Bax agonists for anticancer activity - Wei-Dong Jia; Xue Bai; Qian-Qian Ma; Ming Bian; Chun-Mei Bai; Di Li; Li-Fei Li; Cheng-xi Wei; Li-Jun Yu (Natural Product Research, 2025)

Predicting Lactobacillus delbrueckii subsp. bulgaricus-Streptococcus thermophilus interactions based on a highly accurate semi-supervised learning method - Shujuan Yang; Mei Bai; Weichi Liu; Weicheng Li; Zhi Zhong; Lai-Yu Kwok; Gaifang Dong; Zhihong Sun (Science China Life Sciences, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Corrigendum to “Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis” [J Hazard Mater 468 (2024) 133836] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Genetic dissection of a major locus SC9.1 conferring seed color in broomcorn millet (Panicum miliaceum) - Tianpeng Liu; Kongjun Dong; Jihong He; Mei Wang; Ruiyu Ren; Lei Zhang; Yawei Li; Minxuan Liu; Tianyu Yang (Theoretical and Applied Genetics, 2025)

A stacking ensemble machine learning model for improving monthly runoff prediction - Wen-chuan Wang; Miao Gu; Zong Li; Yang-hao Hong; Hong-fei Zang; Dong-mei Xu (Earth Science Informatics, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Nitrogen fixation of different seasons and parts of seagrass Enhalus acoroides in Xincun Bay, northern South China Sea - Zhen-Zhen Wu; Xiao-Mei Li; Hui Zhao; Long Wei; Jun-De Dong; Mei-Lin Wu (Regional Studies in Marine Science, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Miocene evolution of vegetation, climate, and elevation in the Wulan Basin of northeast Tibetan Plateau based on a CRACLE analysis of palynological assemblages - Xiao-Mei Li; Jia-Yi Chen; Zhen-Dong Cao; Li-Ming Liu; Si-Hang Zhang; Yun-Zhe Zhang; Li-Jie Wei; San-Ping Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A novel daily runoff forecasting model based on global features and enhanced local feature interpretation - Dong-mei Xu; Yang-hao Hong; Wen-chuan Wang; Zong Li; Jun Wang (Journal of Hydrology, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Tectonic-climate-wildfire coupling during the Miocene in the northeastern Qinghai-Tibetan Plateau - Li-Ming Liu; Zhen-Dong Cao; Xiao-Mei Li; Si-Hang Zhang; Yun-Zhe Zhang; Jia-Yi Chen; De-Fei Yan; San-Ping Xie (Journal of Asian Earth Sciences, 2024)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

Morpho-histological and Transcriptome Analysis Reveal the Unreduced Sperm Formation Mechanism in cdk1-Depletion Zebrafish - Yunbang Zhang; Rongyun Li; Hui Li; Yuwei Huang; Yihui Mei; Yuxuan Zheng; Yankun Guo; Zihao Zhou; Zhonglin Yong; Ying Zhao; Wenjing Dong; Jian Gao; et al. (Marine Biotechnology, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

A novel temperature-responsive biphasic deep eutectic solvent-based solvent system: Integrated efficient extraction, enrichment and recovery of phytochemicals - Zi-Hui Cai; Xin-Yue Dong; Li-Tao Wang; Wan-Mei Zhou; Ya-Ning Wang; Jie Yang; Yu-Jie Fu (Chemical Engineering Journal, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Exploring the therapeutic potential of Cassia species on metabolic syndrome: A comprehensive review - Lin Xu; Yue Yang; Bin Li; Hong Dong Liu; Ling Xia Xu; Dong Mei Yan; Xue Mei Gao (South African Journal of Botany, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Revealing the intensification effect of circulating hydrothermal pretreatment: A sustainable route for biorefinery - Feiyue Shen; Chenjun He; Yuhang Wang; Jiayi Xu; Mei Huang; Li Zhao; Jinguang Hu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Construction of artificial microbial consortia for efficient degradation of chicken feathers and optimization of degradation conditions - Wencai Xia; Mei Jin; Xin Li; Chunbo Dong; Yanfeng Han (World Journal of Microbiology and Biotechnology, 2024)

Parametric analysis on mechanical performance and additional reinforcement design method of reinforced concrete chimneys with openings - Zhi-Qian Dong; Gang Li; Song-Ke Zhang; Sha-Yi Wang; Ding-Hao Yu; Zeng-Bo Yao; Chun-Gang Liu; Mei Yang (Bulletin of Earthquake Engineering, 2024)

Alleviation of RO membrane fouling in wastewater reclamation plants using an enhanced acid-base chemical cleaning method - Li Zihao; Jinlong Wang; Lihua Cheng; Qiang Yang; Peizhuo Li; Xiaowan Dong; Boyan Xu; Mei Zhi; Anni Hao; How yong Ng; Xuejun Bi (Water Research, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

Changes of intestinal barrier in the process of intestinal inflammation induced by Aeromonas hydrophila in snakehead (Channa argus) - Xue-qin Wu; Xiu-mei Chen; Yi-yu Pan; Chuang Sun; Jia-xin Tian; Ai-dong Qian; Xiao-tian Niu; Yi-di Kong; Min Li; Gui-qin Wang (Fish & Shellfish Immunology, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Design of multifunctional theranostic nanoplatforms with glutathione-triggered H2S generation and H2S-activitated multi-modal therapy - Cheng Tao; Qian Ren; Nuo Yu; Mei Wen; Pu Qiu; Shining Niu; Zhigang Chen; Kun Li; Dong Xie (Chemical Engineering Journal, 2024)

Warming stimulates mangrove carbon sequestration in rising sea level at their northern limit: An in situ simulation - Peiyang Qiao; Ying Dong; Xiaoxuan Gu; Lian Xu; Mei Li; Wandong Chen; Li Lin; Xiaopin Ni; Luzhen Chen (Limnology and Oceanography, 2024)
Global warming and sea‐level rise are directly influencing the growth, distribution, and greenhouse gas emissions of mangrove forests. However, mangrove forests growing at their latitudinal limits are relatively susceptible to warming; nevertheless, few studies have focused on GHG emissions of latitudinal limits mangrove forests as related to global climate change. To address this knowledge gap, a multiyear in situ control experiment was established in a restored plantation at the northern distribution limit of Kandelia obovata , the most cold‐tolerant mangrove species in China, to simulate both warming and sea‐level rise. We investigated the growth patterns and sediment greenhouse gas emissions of a K. obovata population and identified the primary factors contributing to these changes. The results showed that warming and moderate sea‐level rise enhanced biomass by more than 18%, indicating that warming stimulated plant growth while excessive sea‐level rise inhibited it. The sediment greenhouse gas emissions ranged from 45.5 to 484.6 mgCO 2 m −2 h −1 , 5.6 to 590.3 μ gCH 4 m −2 h −1 , and 11.4 to 385 μ gN 2 O m −2 h −1 , which increased with warming while decreased with sea‐level rise, acting as the net source of greenhouse gas emission. Our study predicted that sea‐level rise, while directly changing sediment properties, had combined effects with warming on these studied mangrove forests that were predicted to emit more greenhouse gases from sediments in the future. These findings indicated that K. obovata plantations within their latitudinal limits tend to accumulate more CO 2 for biomass carbon storage under warming conditions, while stimulating sediment greenhouse gas emissions, which will offset their climate mitigating effect in future climatic scenarios.

Enhanced degradation of emerging contaminants by Far-UVC photolysis of peracetic acid: Synergistic effect and mechanisms - Chen-Yan Hu; Li-Li Hu; Zheng-Yu Dong; Xin-Yu Yang; Hao Liu; Jia-Nan Chen; Ling-Mei Gao (Water Research, 2024)

Effects of nitrogen regulation on heavy metal phytoextraction efficiency (Leucaena leucocephala): Application of a nitrogen fertilizer and a fungal agent - Chao Liu; Jiayi Liu; Xiaoli Mei; Jiaxin Zheng; Kang Zheng; Ou Li; Chonlong Chio; Janak Khatiwada; Xiaoxia Zhang; Dong Wang; Haibo Hu; Wensheng Qin; et al. (Environmental Pollution, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Dual dynamic network structures of recyclable epoxy resins with high strength and toughness via sacrificial hydrogen-bonding clusters and imine bonds: surpassing the strength-toughness trade-off - Cheng-wang Shi; Xiao-dong Li; Xu-feng Zhang; Mei-shuai Zou (Chemical Engineering Journal, 2024)

Development of Sugar Industry in China: R&D Priorities for Sustainable Sugarcane Production - Yang-Rui Li; Bao-Qing Zhang; Xiu-Peng Song; Qiang Liang; Krishan K. Verma; Dong-Mei Li (Sugar Tech, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Seismic response characteristics of shield tunnel structures in liquefiable soils - Yiyao Shen; M. Hesham El Naggar; Dong-Mei Zhang; Liyun Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2024)

Screening of superior wheat lines under nitrogen regulation and factors affecting grain quality improvement under high yield - Chuan Zhong; Zhaowei Zhang; Mei Huang; Qing Li; Yingxin Zhong; Xiao Wang; Jian Cai; Tingbo Dai; Qin Zhou; Dong Jiang (Journal of Cereal Science, 2024)

Defect-decorated Cu2MoS4 as a new efficient hydrogen evolution cocatalyst: Rich active sites, rapid charge transfer and optimized hydrogen adsorption - Mei Dong; Wenjun Li; Liang Geng; Xiaohui Ma; Yajie Li; Yueyan Fan; Ajmal Khan (Fuel, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Human health risk assessment and toxic effect of heavy metal(loid)s in Bamboo shoot products - Yu-Mei Xie; Meng-Yan Zhang; Fei-Peng Liu; Cheng-Chen Wang; Wen-Yuan Dong; Chun-Mei Xu; Xin Li; Wu-Mei Xu; Ping Xiang (Journal of Environmental Chemical Engineering, 2024)

Reproductive toxicity of PFOA, PFOS and their substitutes: A review based on epidemiological and toxicological evidence - Wenshan Shi; Zengli Zhang; Mei Li; Huiyu Dong; Jiafu Li (Environmental Research, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Genetic contribution and decision-making coefficients analysis of agronomic components of upland cotton in Southern Xinjiang to yield traits - Changxi Li; Yonghu Guan; Zhanpeng Dong; Yongjun Mei (Euphytica, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

A comparative study on the nutritional composition, protein structure and effects on gut microbiota of 5 fermented soybean products (FSPs) - Xinyu Miao; Honghong Niu; Mubai Sun; Xin Dong; Mei Hua; Ying Su; Jinghui Wang; Da Li (Food Research International, 2024)

An oxygen isotope perspective on the break-up of the Rodinia supercontinent - Hao Zou; Chang-Cheng Huang; Hua-Wen Cao; Chun-Mei Liu; Hui-Dong Yu; Franco Pirajno; Xian-Hua Li (Earth-Science Reviews, 2024)

Effect of multi-interface electron transportation and molecule adsorption on hydrogen evolution reaction - Xinyu Zhang; Zhihui Li; Xiaoman Yang; Hanming Zhang; Dan Wang; Zhian Li; Chengyue Han; Bingzheng Dong; Zhisheng Mei; Fei Teng (Chemical Engineering Journal, 2024)

Reaction-induced restructuring of partial Pd single atoms to nanoparticles for enhancing HMF selective hydrogenation to BHMTHF - Xiangyu Jia; Kai Yuan; Guofu Wang; Shanhui Zhu; Mei Dong; Jiamin Wang; Xiaoming Li; Weibin Fan (Chemical Engineering Journal, 2024)

A new diterpenoid from the leaves and twigs of Croton lachnocarpus Benth - Xiao-Qing Zhan; Qian Wu; Mei-Jie Wang; Li Liu; Wen-Bo Cui; Feng-Li An; Feng-Ming Qi; Dong-Qing Fei; Zhan-Xin Zhang (Natural Product Research, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Effects of Dietary Zinc on Growth Performance, Digestive Enzyme Activities, Antioxidant Status, and Immune Responses of Sea Cucumber Apostichopus japonicus - Yuling Xu; Qinfeng Gao; Shuanglin Dong; Zhishuai Hou; Yaoping Mei; Xueqi Li; Kang Dong; Zhao Li (Biological Trace Element Research, 2024)

Impact of ecological migration village construction on vector mosquito and mosquito-borne disease in the southern Yunnan Province, China - Mei-De Liu; Chun-Xiao Li; Xue-Zhong Wang; Yan-De Dong; Tong-Yan Zhao (International Journal of Tropical Insect Science, 2024)
To evaluate the influence of ecological migration village construction on mosquito vector populations and mosquito-borne diseases in southern Yunnan Province. Two vicinal villages in Mengla County, the southern part of Yunnan Province, a native village, and a newly built village, were selected as study sites. Malaria and Japanese Encephalitis vector mosquito population divergence between the two villages were studied. Malaria and Japanese Encephalitis (JE) cases in the two villages were also compared. Anopheles minimus was the dominant population in houses in the newly built village, and An . jeyporiensis dominated the native village. Accordingly, there were nine malaria cases in the new village compared with zero cases in the native village. Culex tritaeniorhynchus , the chief JE vector in the study area, displayed no difference between the two villages; however, there was a higher density of the local secondary JE vector ( Cx. pseudovishnui ) in the native village than in the new one. The JE cases in the villages corresponded to zero. From the vector-borne disease perspective, our results suggest that local community should pay more attention to malaria and An . minimus during the construction of an ecological migration village in the new Chinese Western Developing Plan (CWDP) in southern Yunnan Province.

How does adsorptive fractionation of dissolved black carbon on ferrihydrite affect its copper binding behaviors? A molecular-scale investigation - Mei Huang; Qi Yang; Jianmei Zou; Li Zhao; Jinsong He; Dong Tian; Yongjia Lei; Fei Shen (Water Research, 2024)

Effects of chronic low-level lead (Pb) exposure on cognitive function and hippocampal neuronal ferroptosis: An integrative approach using bioinformatics analysis, machine learning, and experimental validation - Yingsi Cao; Wenjing Zhao; Yanqi Zhong; Xiaofan Jiang; Huiya Mei; Yuanjin Chang; Dongqin Wu; JianRui Dou; Emely Vasquez; Xian Shi; Jiatao Yang; Zhongtang Jia; et al. (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

Effect of sulfide on the physiological energetics of Mercenaria mercenaria - Xuan-zhao Zhang; Mei-jie Yang; Cong Zhou; Hao Song; Shi-peng Dong; Yong-jun Guo; Yong-ren Li; Fang Wang; Tao Zhang (Aquaculture, 2024)

Enhancing soil carbon and nitrogen through grassland conversion from degraded croplands in China: Assessing magnitudes and identifying key drivers of phosphorus reduction - Yuan Li; Ying Li; Qingping Zhang; Gang Xu; Guopeng Liang; Dong-Gill Kim; Carmen Rosa Carmona; Mei Yang; Jianming Xue; Yangzhou Xiang; Bin Yao; Yuying Shen (Soil and Tillage Research, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Two unprecedented 2-(2-phenethyl)chromone dimers from red soil agarwood of Aquilaria crassna - Hong-Xing Chai; Hao Wang; Jun Zeng; Wen-Hua Dong; Wen-Li Mei; Bei Jiang; Wei Li; Hao-Fu Dai (Phytochemistry Letters, 2024)

An ensemble model for monthly runoff prediction using least squares support vector machine based on variational modal decomposition with dung beetle optimization algorithm and error correction strategy - Dong-mei Xu; Zong Li; Wen-chuan Wang (Journal of Hydrology, 2024)

Bright photoactivatable probes based on triphenylethylene for Cu2+ detection in tap water and tea samples - Zuo-Qin Liang; Dong-Dong Song; Zhuo-Cheng Li; Su-Hang Xu; Guo-Liang Dai; Chang-Qing Ye; Xiao-Mei Wang; Xu-Tang Tao (Food Chemistry, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of arbuscular mycorrhizal fungi on uptake, partitioning and use efficiency of nitrogen in wheat - Jiawen Xue; Lili Guo; Liulong Li; Zhaowei Zhang; Mei Huang; Jian Cai; Xiao Wang; Yingxin Zhong; Tingbo Dai; Dong Jiang; Qin Zhou (Field Crops Research, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Correlational analysis of physicochemical indexes, microbial communities, and volatile components in light-flavor Daqu from north and south regions of China - Qi Yu; Feiyan Mou; Junwen Xiao; Cheng Zhan; Liang Li; Xu Chang; Xiaoyuan Dong; Maobin Chen; Xinrui Wang; Mei Chen; Shangling Fang (World Journal of Microbiology and Biotechnology, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Local-enhanced multi-scale aggregation swin transformer for semantic segmentation of high-resolution remote sensing images - Dong Ren; Falin Li; Hang Sun; Li Liu; Shun Ren; Mei Yu (International Journal of Remote Sensing, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

The swelling induced choline alkali-urea (SICAU) process for sustainable crop straw upgrading - Yuehan Jiang; Feiyue Shen; Baiheng Jiang; Yuheng Hu; Jinguang Hu; Mei Huang; Li Zhao; Hejun Wu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Extraction of super high-yield lignin-carbohydrate complexes from rice straw without compromising cellulose hydrolysis - Baiheng Jiang; Feiyue Shen; Yuehan Jiang; Mei Huang; Li Zhao; Yongjia Lei; Jinguang Hu; Dong Tian; Fei Shen (Carbohydrate Polymers, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

An efficient approach to utilize copper smelting slag: Separating nonferrous metals and reducing iron oxide at high temperature - Liushun Wu; Hui Li; Kunlong Liu; Haiqing Mei; Yunjin Xia; Yuanchi Dong (Waste Management, 2023)

A novel approach to accelerate carbon dioxide sequestration of ladle furnace slag using sodium bicarbonate solution - Liushun Wu; Hui Li; Haiqing Mei; Lei Rao; Yunjin Xia; Yuanchi Dong (Minerals Engineering, 2023)

Development and characterization of self-emulsifying high internal phase emulsions using endogenous phospholipids from Antarctic krill oil - Dong-wen Fu; Jing-jing Li; Dong-mei Dai; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Chemistry, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Constructing DNA Fingerprinting and Evaluating Genetic Diversity Among Sugar Beet (Beta vulgaris L.) Varieties Based on Four Molecular Markers - Xue-Mei Liang; Zhi Pi; Ze-Dong Wu; Sheng-Nan Li (Sugar Tech, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Transcriptome Analysis Reveals New Insights into the Respiration Metabolism Mechanism of Different Feeding Rations of Sea Cucumber (Apostichopus japonicus) - Yaoping Mei; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong; Xueqi Li; Yuling Xu (Journal of Ocean University of China, 2023)

Three new triterpenoid glycosides from Aronia melanocarpa (Michx.) Elliott - Ting-Ting Guo; Man-Li Zhang; Zhao-Cui Sun; Li-Mei Zhang; Xu-Dong Xu; Bi-Huang Hu (Natural Product Research, 2023)

Novel GdTaO4 phase for efficient photocatalytic degradation of organic dye under visible light irradiation: An X-ray spectroscopic investigation - Alageshwaramoorthy Krishnaprasanth; Pandian Mannu; Seetha Mahalingam; Dhanaprabhu Pattappan; Asokan Kandasami; Yi-Ting Lai; Yoshitake Masuda; Han-Wei Chang; Mei-Yu Chen; Ping-Hung Yeh; Chung-Li Dong (Chemosphere, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Integrating ATAC-seq and RNA-seq to identify differentially expressed genes with chromatin-accessible changes during photosynthetic establishment in Populus leaves - Sheng-Ying Zhang; Biligen-Gaowa Zhao; Zhuo Shen; Ying-Chang Mei; Guo Li; Feng-Qin Dong; Jiao Zhang; Qing Chao; Bai-Chen Wang (Plant Molecular Biology, 2023)

Paraburkholderia flagellata sp. nov. and Paraburkholderia adhaesiva sp. nov., two novel species isolated from forest soil in Dinghushan Biosphere Reserve in Guangdong, China - Xiu-yin Guo; Ke-cheng Wu; Cheng-zhi Dong; Qiu-mei Zhang; Li-hong Qiu (Antonie van Leeuwenhoek, 2023)

Megastigmane sesquiterpenoids from Saussurea medusa and their anti-inflammatory activities - Jing-Ya Cao; Qi Dong; Zhi-Yao Wang; Ye Zhao; Yu Ren; Li-Juan Mei; Yan-duo Tao; Rui-Tao Yu (Natural Product Research, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

A new insight of water inrush mode and coal (rock) pillars setting in near-fault mining under high confined water - Fangying Dong; Huiyong Yin; Qingfu Feng; Shuo Li; Wei Zhou; Wenju Cheng; Mei Qiu; Yongli Shi; Chuanwei Jia (Journal of Applied Geophysics, 2023)

Cascade utilization of crop straw through a FeCl3-mediated deep eutectic solvent biorefinery: Lignin-containing cellulose nanofibers flocculant fabrication followed by fertilizer production - Yiyi Chen; Chaojie Yang; Jinguang Hu; Mei Huang; Li Zhao; Jinsong He; Shaobo Zhang; Fei Shen; Dong Tian (Chemical Engineering Journal, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Reduced dietary Ca, Cu, Zn, Mn, and Mg bioavailability but increased Fe bioavailability with polyethylene microplastic ingestion in a mouse model: Changes in intestinal permeability and gut metabolites - Shan Chen; Shi-Wei Li; Xue-Yuan Gu; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Science of The Total Environment, 2023)

Efficient removal of heavy metals from aqueous solutions using Mn-doped FeOOH: Performance and mechanisms - Mei Li; Yan Kang; Haoqin Ma; Jiahao Dong; Yuqi Wang; Shaoping Kuang (Environmental Research, 2023)

Multi-Color Room temperature phosphorescent Silicon-Nanodot-Based nanocomposites with silane tuning and applications to 5D information encryption - Yulu Liu; Lei Cao; Panyong Wang; Xinpei Pang; Li Li; Qian Mei; Wen-Fei Dong; Minghui Zan (Chemical Engineering Journal, 2023)

Static magnetic field increases aerobic nitrogen removal from hypersaline wastewater in activated sludge with coexistence of fungi and bacteria - Jun Chen; You-Wei Cui; Mei-Qi Huang; Hui-Juan Yan; Dong Li (Bioresource Technology, 2023)

Understanding the spatiotemporal variation of ride-hailing orders under different travel distances - Xuefeng Li; Jiacong Xu; Mingyang Du; Dong Liu; Mei-Po Kwan (Travel Behaviour and Society, 2023)

Fully upgrade lignocellulose to three nanomaterials by combinational pretreatment: Refining straw waste to pesticide nanocarrier - Feiyue Shen; Chenjun He; Yuhang Wang; Jinguang Hu; Mei Huang; Li Zhao; Shaobo Zhang; Dong Tian; Fei Shen (Chemical Engineering Journal, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Bisabolane and drimane sesquiterpenes from the fungus Coprinellus sp. - Mei-Jing Chi; Xin-Yue Dong; Wen-Ke Wei; Xue-Mei Li; Xiao-Jun Li; Ji-Kai Liu; Tao Feng (Phytochemistry Letters, 2023)

Spatiotemporal changes of agricultural water footprint and its driving factors using the ARDL model in the Hexi corridor, China - Jun Zhang; Hui-xia Yang; Fan Zhou; Jia-liang Li; Dong-mei Zhou; Guo-zhang Cen; Jing Ma; Xiao-yan Zhu (Journal of Arid Environments, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Higher resistance of a microcystin (MC)-producing cyanobacterium, Microcystis, to the submerged macrophyte Myriophyllum spicatum - Yunni Gao; Hui Yang; Longfei Li; Xiaofei Gao; Mei Li; Jing Dong; Man Zhang; Jingxiao Zhang; Xuejun Li; Zhiying Lu; Michele A. Burford (Environmental Science and Pollution Research, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Cycloartane triterpene glycosides from Actaea vaginata - Min-Li Zhang; Yi-Min Li; Zi-Xuan Zhao; Xiang-Yuan Li; Zhao-Cui Sun; Guo-Xu Ma; Mei-Hua Yang; Xu-Dong Xu; Xiao-Feng Zhang; Hai-Feng Wu; Qiong-Yu Zou; Nelbon Giloi (Phytochemistry Letters, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Enhancement of perfluorooctanoic acid and perfluorooctane sulphonic acid removal in constructed wetland using iron mineral: Performance and mechanisms - Haoqin Ma; Yan Kang; Mei Li; Jiahao Dong; Yuqi Wang; Jingqian Xiao; Zizhang Guo (Journal of Hazardous Materials, 2023)

Combined biological effects of polystyrene microplastics and phenanthrene on Tubifex tubifex and microorganisms in wetland sediment - Jiahao Dong; Yan Kang; Shaoping Kuang; Haoqin Ma; Mei Li; Jingqian Xiao; Yafei Wang; Zizhang Guo; Haiming Wu (Chemical Engineering Journal, 2023)

High bioethanol titer and yield from phosphoric acid plus hydrogen peroxide pretreated paper mulberry wood through optimization of simultaneous saccharification and fermentation - Pleasure Chisom Ajayo; Qing Wang; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Dexin Fang; Jinguang Hu; Fei Shen (Bioresource Technology, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Influence of multiple islands on the hysteresis and dynamics of a western boundary current perturbed by a mesoscale eddy at a gap - Kunshan Li; Huan Mei; Xiangbai Wu; Jianxin Dong; Qian Liu (Frontiers in Marine Science, 2023)
The hysteresis of a western boundary current (WBC) flowing across a gap and the dynamics of the mesoscale eddy–WBC interaction with the presence of two islands in the gap are studied using a 1.5-layer ocean model. The hysteresis of the WBC suggests that the two islands in the gap facilitate the WBC to intrude into the western basin by shedding eddies compared with the no-island case, but they promote the WBC to leap across the gap compared with the one-island case. The mesoscale eddies from the east of the gap can induce the critical-state WBC shifting from penetration to leap and vice versa. The dynamics revealed by the vorticity balance analysis shows that the increased (decreased) meridional advection of the WBC perturbed by the eddy forces the WBC to leap across (intrude into the western basin through) the gap. We also present the parameter space of the critical strength of the eddy with variable north–south locations inducing the critical WBC transition. For the WBC critical from the eddy-shedding to leaping regime, the regime shift is most sensitive to the anticyclonic eddy from the gap center and to the cyclonic eddy from the southern gap. It is least sensitive to the eddy downstream of the WBC. For the WBC critical from the leaping to eddy-shedding regime, the regime shift is most sensitive to the anticyclonic eddy upstream of the WBC and to the cyclonic eddy from the southern gap. The least sensitive eddy is from the northern gap.

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Structural and functional properties of sodium caseinate glycosylated by dextran aldehyde - Ying Li; Dong-Mei Li; Yu Han; Xin-An Zeng; Zhong Han (Food Chemistry, 2023)

Analysis of the main effect clustering and decision-making coefficients for F2 generation of upland cotton in Southern Xinjiang - Hong Guo; Jiwen Yu; Wenfeng Pei; Yonghu Guan; Hang Li; Changxi Li; Jinwei Liu; Wei Wang; Zhanpeng Dong; Baoquan Wang; Yongjun Mei (Euphytica, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Glyphosate based-herbicide disrupts energy metabolism and activates inflammatory response through oxidative stress in mice liver - Lei Qi; Yan-Mei Dong; Hong Chao; Peng Zhao; Shu-Li Ma; Gang Li (Chemosphere, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Application of dual-solvent extraction for separating a low-temperature coal tar: A detailed experimental and quantum chemical study - Zhi-Hao Ma; Sheng Li; Chun Guo; Xue-Qian Dong; Jin-Hu Wang; Min Li; Xian-Hou Guo; Mei-Ling Xu; Xing-Shun Cong; Zhi-Min Zong; Xian-Yong Wei (Fuel, 2023)

Controllable preparation of ultrafine Co3O4 nanoparticles on H-ZSM-5 with superior catalytic performance in lean methane combustion - Chao Fan; Zhiwei Wu; Zhikai Li; Zhangfeng Qin; Huaqing Zhu; Mei Dong; Jianguo Wang; Weibin Fan (Fuel, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

The anti-TMV potency of the tobacco-derived fungus Aspergillus versicolor and its active alkaloids, as anti-TMV activity inhibitors - Jia-Meng Dai; Qi-Li Mi; Xue-Mei Li; Du Gang; Guang-Yu Yang; Jian-Duo Zhang; Jin Wang; Yin-Ke Li; Hai-Ying Yang; Dong Miao; Zhen-Jie Li; Qiu-Fen Hu (Phytochemistry, 2023)

Bioaccumulation of Cd and comparative transcriptome analysis after the antagonism of Se in the hepatopancreas of estuary mud crab (Scylla paramamosain) - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wei-Ren Dong; Miao-An Shu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

A new water-soluble lignin incorporation enhanced the barrier performance of liquid mulching film - Dong Tian; Jing Zhang; Jinguang Hu; Mei Huang; Li Zhao; Yongjia Lei; Jianmei Zou; Shaobo Zhang; Fei Shen (Chemical Engineering Journal, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Multiple habitat templates for phytoplankton indicators within the functional group system - Man Zhang; Xucong Lv; Jing Dong; Yunni Gao; Jingxiao Zhang; Mei Li; Xiaofei Gao; Xuejun Li (Hydrobiologia, 2023)

Establishment of adventitious root culture system of Cynanchum wilfordii in air-lift bioreactors for the efficient production of bioactive compounds - Mei Wang; Miao Wang; Dong An; Chun-Hua Wu; Guang Li; Wei Wang; Xiao-Song Zhang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2022)

Association between short- and long-term exposures to air pollutants and internalizing/externalizing behavior in children aged 4 to 7 years - Haiqin Qi; Anna Peng; Hong Mei; Yuanyuan Zhang; Ya Zhang; Paiziyeti Tuerxun; Wenli Dong; Chunan Li; Ke Xu; Ruixia Chang; Shaoping Yang; Jianduan Zhang (Environmental Science and Pollution Research, 2022)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Comparison of infections with respiratory syncytial virus between children and adults: a multicenter surveillance from 2015 to 2019 in Beijing, China - Ming Luo; Cheng Gong; Yan Zhang; Xue Wang; Yang Liu; Qing Luo; Maozhong Li; Aihua Li; Yiting Wang; Mei Dong; Wenbo Xu; Fang Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Characteristic pollutants risk assessment of modified manganese residue utilization in sintered product - Chao-qiang Wang; Ke Liu; De-ming Huang; Qi-cong Huang; Pei-xin Wang; Xu-dong Mei; Shu-chun Li (Environmental Science and Pollution Research, 2022)

Trace element signature of hydrothermal quartz: a potential tracer for ore genesis - Juan Dong; Li-Bin Jia; Mei-jia Song; Shu-Teng Xu; Mao-Wen Yuan; Cheng-Lu Li; Yuan-Jiang Yang (Arabian Journal of Geosciences, 2022)

Effects of rainfall and rocky desertification on soil erosion in karst area of Southwest China - Li-dong Pan; Rui Li; Dong-cai Shu; Li-na Zhao; Mei Chen; Jun Jing (Journal of Mountain Science, 2022)

Responses of submerged macrophyte Ceratophyllum demersum to the gradient concentrations of microcystin-LR (MC-LR) - Jing Dong; Dujuan Dai; Yue Yang; Feihu Wang; Xuejun Li; Jie Yuan; Yuhuan Chen; Yunni Gao; Man Zhang; Xiaofei Gao; Mei Li; Jingxiao Zhang (Environmental Science and Pollution Research, 2022)

Feeding behavior, microcystin accumulation, biochemical response, and ultramicrostructure changes in edible freshwater bivalve Corbicula fluminea exposed to Microcystis aeruginosa - Jingxiao Zhang; Miao Yu; Yunni Gao; Man Zhang; Jing Dong; Mei Li; Xuejun Li (Environmental Science and Pollution Research, 2022)

Ecological damage of submerged macrophyte Myriophyllum spicatum by cell extracts from microcystin (MC)- and non-MC-producing cyanobacteria, Microcystis - Yunni Gao; Hui Yang; Xiaofei Gao; Mei Li; Man Zhang; Jing Dong; Jingxiao Zhang; Longfei Li; Xuejun Li; Michele A Burford (Journal of Oceanology and Limnology, 2022)

Potential Specificity Between Mycorrhizal Fungi Isolated from Widespread Dendrobium spp. and Rare D. huoshanense Seeds - Yan-Jing Tang; Dong-Yu Zhou; Jun Dai; Yang Li; Yong-Mei Xing; Shun-Xing Guo; Juan Chen (Current Microbiology, 2022)

Temporal specificity of IL-6 knockout in enhancing the thermogenic capability of brown adipose tissue - Mei Dong; Cheng Gao; Yanxin Jia; Weijia Xu; Yan Liu; Xin Wen; Qingxin Liu; Hai Lin; Haifang Li (Journal of Physiology and Biochemistry, 2022)

MdMYB88/124 modulates apple tree microRNA biogenesis through post-transcription processing and/or transcription pathway - Chun-dong Niu; Huan-ran Shi; Zi-tong Zhang; Tian-le Fan; Huan Dang; Peng-xiang Chen; Yin-peng Xie; Cha-na Bao; Feng-wang Ma; Qing-mei Guan; Xue-wei Li (Acta Physiologiae Plantarum, 2022)

Effects of different stocking densities on the CO2 fluxes at water-air interface and the respiration metabolism in sea cucumber Apostichopus japonicus (Selenka) - Yaoping Mei; Yuan Tian; Qinfeng Gao; Shuanglin Dong; Xueqi Li; Yuling Xu (Frontiers in Marine Science, 2022)
Recently, abundant research has been devoted to investigating the variations of CO 2 concentration in the atmosphere. However, the information of CO 2 fluxes at the water-air interface remains limited, especially those from the respiratory metabolism of aquatic organisms. In the present study, a comprehensive analysis was carried out to evaluate the effects of different stocking densities of sea cucumber ( Apostichopus japonicus ) on the CO 2 fluxes at water-air interface, and to explore the relationships between CO 2 fluxes and respiratory metabolism. A total of 60 sea cucumbers were randomly classified into 4 groups with different stocking densities, including 2, 5 and 8 ind./tank (namely D2, D5 and D8 groups). After 34-day feeding trial, individuals in D5 had superior growth performance rather than D2 and D8. The analysis of modified floating static chambers clearly showed that the mean CO 2 flux at the water-air interface in D5 was significantly higher than D2 and D8. Meanwhile, energy budget analysis revealed that D5 had higher carbon and nitrogen utilization, excretion energy and metabolizable energy, suggesting relatively active respiration metabolism in moderate stocking density. The activities of pyruvate dehydrogenase (PDH) and α-ketoglutarate dehydrogenase (OGDH) in respiratory tree and body wall tissues provided additional evidence for the higher respiration metabolism rate of individuals at D5, which may be responsible for the higher CO 2 fluxes at the water-air interface. Transcriptome analysis was performed to uncover the molecular mechanism of respiratory metabolism affected by different stocking densities. The differentially expressed genes in respiration trees and body walls were significantly enriched in peroxisome, fatty acid degradation, and oxidative phosphorylation pathways. It may explain the differences of respiration metabolism rates at different stocking densities. The present study preliminarily revealed the CO 2 fluxes variation at the water-air interface from aquatic invertebrates, and provided the scientific basis for the efficient and low-carbon agricultural technologies of sea cucumber.

Millifolide A, a dimeric ether of degraded sesquiterpene lactones, inhibited the proliferation of human lung cancer cell line A549 - Pan-Pan Yu; Feng Yu; Wen-Zhe Li; Si-Ming Wang; Chuan Wang; Mei Dong; Zhi-Yu Ni; Yong Li; Hiromasa Kiyota (Natural Product Research, 2022)

Spatial relationship among the density of Culex tritaeniorhynchus, Anopheles sinensis, human dwellings and pigsty in Guangxi, China: modelling study - Mei-De Liu; Chun-Xiao Li; Xiang-Yang Feng; Yan-De Dong; Mi-You Yi; Tong-Yan Zhao (International Journal of Tropical Insect Science, 2022)

Three-dimensional modelling of stress relaxation of soft clay under complex loading conditions - Jian Li; Dong-Mei Zhang; Pierre-Yves Hicher; Chang-Fu Wei (European Journal of Environmental and Civil Engineering, 2022)

Phenolic compounds from the sclerotia of Inonotus obliquus - Yan-Mei Wei; Li Yang; Wen-Li Mei; Hui-Qin Chen; Cai-Hong Cai; Wei Li; Wen-Hua Dong; Zhi-Bao Chen; Hao-Fu Dai (Natural Product Research, 2022)

PdeHCA2 affects biomass in Populus by regulating plant architecture, the transition from primary to secondary growth, and photosynthesis - Biligen-Gaowa Zhao; Guo Li; Yue-Feng Wang; Zhen Yan; Feng-Qin Dong; Ying-Chang Mei; Wei Zeng; Meng-Zhu Lu; Hong-Bin Li; Qing Chao; Bai-Chen Wang (Planta, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

New ursolic acid derivatives bearing 1,2,3-triazole moieties: design, synthesis and anti-inflammatory activity in vitro and in vivo - Tian-Yi Zhang; Chun-Shi Li; Li-Ting Cao; Xue-Qian Bai; Dong-Hai Zhao; Si-Mei Sun (Molecular Diversity, 2022)

Real-world PM2.5 exposure induces pathological injury and DNA damage associated with miRNAs and DNA methylation alteration in rat lungs - Lifang Zhao; Mei Zhang; Lirong Bai; Yufei Zhao; Zongwei Cai; Ken Kin Lam Yung; Chuan Dong; Ruijin Li (Environmental Science and Pollution Research, 2022)

Inhibition of red chlorophyll catabolite reductase improved chlorophyll and carotenoid synthesis in tobacco - Chen Dong; Mei Zhang; Fang Wei; Yushuang Guo; Lili Qin; Pan Wei; Yubo Wang; Lifeng Jin; Weina Song; Tao Sun; Feng Li; Ran Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Persistence of Digestive Enzyme Activities of Sea Cucumber (Apostichopus japonicus): Evidence From Diet Switch After Evisceration - Xueqi Li; Qinfeng Gao; Yuan Tian; Yaoping Mei; Yuling Xu; Yiming Cao; Shuanglin Dong; Yangen Zhou; Yongjun Sun; Wenming Ju (Frontiers in Marine Science, 2022)
A two-stage diet-switch experiment was conducted to examine the hypothesis that the changes in digestive enzyme activities of sea cucumber ( Apostichopus japonicus ) induced by historic diets might persist in the regenerated intestines. In stage I, A. japonicus were treated with two different diets for 56 days, including diet A with 11% crude protein, 1% crude lipid, and 40% carbohydrate, and diet B with 18% crude protein, 2% crude lipid, and 35% carbohydrate. In stage II, each treatment was subjected to evisceration with 0.35M KCl or not (eviscerated and non-eviscerated groups), half of which were then switched to different diets from diet A to B or vice versa for 112 days. The persistence of digestive enzyme activities was evaluated by measuring the changes in digestive enzyme activities before and after evisceration. In stage I, diets B and A increased trypsin and amylase activities, respectively. In stage II, the higher trypsin activities were observed in eviscerated and non-eviscerated A. japonicus that had consumed diet B in stage I. The higher amylase activities were observed only in eviscerated A. japonicus that had consumed diet A in stage I. It indicated that the historic diets showed long-term effects on the digestion of A. japonicus , which led to the persistence of changes in both trypsin and amylase activities in intestines, especially in the regenerated intestines. In addition, the specific growth rates (SGRs) and metabolic rates (MRs) of A. japonicus were affected by the long-term effects of historic diets. Meanwhile, the relationships between enzymic activities, SGRs, and MRs were observed in A. japonicus , indicating that the historic diets could produce long-term effects on the growth and metabolism of A. japonicus through their long-term effects of historic diets on digestive enzyme activities. In conclusion, the present study showed that the changes in digestive enzyme activities induced by different diets in stage I could persist in the intestines and regenerated intestines, leading to long-term effects of historic diets on the growth and metabolism of A. japonicus .

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Protein Kinase C Controls the Excitability of Cortical Pyramidal Neurons by Regulating Kv2.2 Channel Activity - Zhaoyang Li; Wenhao Dong; Xinyuan Zhang; Jun-Mei Lu; Yan-Ai Mei; Changlong Hu (Neuroscience Bulletin, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Azospirillum tabaci sp. nov., a bacterium isolated from rhizosphere soil of Nicotiana tabacum L - Yan-Qing Duan; Xing-Kui Zhou; Neeli Habib; Shi-Qiang Gao; Li-Min Dong; Xiao-Fei Liu; Yang-Mei Shi; Wen-Jun Li; Gang Du (Archives of Microbiology, 2022)

Antimicrobial Natural Products Produced by Soil-Derived Fungus Penicillium cremeogriseum W1-1 - Xu-Yan Sang; Zhao-Jie Wang; Ya-Bin Yang; Yong-Liang Wang; Mei-Ling Xiang; Dou-Ying Zhu; Ying Zhou; Xiao-Dong Luo; Li-Xing Zhao (Indian Journal of Microbiology, 2021)

Effects of Supplementary Selenium and Vitamin E on the Growth Performance, Antioxidant Enzyme Activity, and Gene Expression of Sea Cucumber Apostichopus japonicus - Yuling Xu; Qinfeng Gao; Shuanglin Dong; Yaoping Mei; Xueqi Li (Biological Trace Element Research, 2021)

Long-term changes of water acidity in an intact forested watershed in south China - Xiao-dong Liu; Ying-jie Feng; Qi-feng Mo; Guo-wei Chu; Yue-lin Li; Qian-mei Zhang; Wei-qiang Zhang; Xian-hua Gan; Qing Zhou (Journal of Mountain Science, 2021)

Characterization and identification of SFDC ‐1, a novel AmpC ‐type β‐lactamase in Serratia fonticola - Xu Dong; Peiyao Zhang; Kexin Zhou; Jialei Liang; Qiaoling Li; Xueya Zhang; Danying Zhou; Wei Lu; Zhewei Sun; Hongmao Liu; Junwan Lu; Xi Lin; et al. (Environmental Microbiology, 2021)
Summary The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1 , although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis - Pan Xiang; Wen-Hua Dong; Cai-Hong Cai; Wei Li; Li-Man Zhou; Hao-Fu Dai; Hui-Qin Chen; Wen-Li Mei (Natural Product Research, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

A new ergostane derivative from the leaves of Heynea trijuga Roxburgh - Shou-Bai Liu; Zheng Cui; Hui-Qin Chen; Hao Wang; Wen-Hua Dong; Cai-Hong Cai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Randomized, placebo-controlled trial of orally administered vitamin K1 for warfarin-associated coagulopathy in Chinese patients with mechanical heart valves - Heng Zhang; Mei Li; Xue-lian Ao; Yi-jun Dong; Li Dong (European Journal of Clinical Pharmacology, 2021)

Apigenin Improves Hypertension and Cardiac Hypertrophy Through Modulating NADPH Oxidase-Dependent ROS Generation and Cytokines in Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Han-Bo Hu; Qian-Wen Yang; Kai-Li Liu; Yan-Mei Chen; Yan Zhang; Dong-Dong Zhang; Hua Tian; Guo-Qing Zhu; Jie Qi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Protective effects of astaxanthin from Haematococcus pluvialis on the survival and oxidative stress of zebrafish embryos induced by microcystin-LR - Jing Dong; Chenlu Li; Dujuan Dai; Man Zhang; Yunni Gao; Xuejun Li; Mei Li; Jingxiao Zhang; Xianfeng Wang; Chuanjiang Zhou (Journal of Applied Phycology, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

Underwater Image Restoration via Non-Convex Non-Smooth Variation and Thermal Exchange Optimization - Qingliang Jiao; Ming Liu; Pengyu Li; Liquan Dong; Mei Hui; Lingqin Kong; Yuejin Zhao (Journal of Marine Science and Engineering, 2021)
The quality of underwater images is an important problem for resource detection. However, the light scattering and plankton in water can impact the quality of underwater images. In this paper, a novel underwater image restoration based on non-convex, non-smooth variation and thermal exchange optimization is proposed. Firstly, the underwater dark channel prior is used to estimate the rough transmission map. Secondly, the rough transmission map is refined by the proposed adaptive non-convex non-smooth variation. Then, Thermal Exchange Optimization is applied to compensate for the red channel of underwater images. Finally, the restored image can be estimated via the image formation model. The results show that the proposed algorithm can output high-quality images, according to qualitative and quantitative analysis.

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Impact of solar ultraviolet radiation on daily outpatient visits of atopic dermatitis in Shanghai, China - Hui-jing Gu; Li Peng; Wen-cai Jiang; Yi-mei Tan; Guo-jiang Zhou; Hai-dong Kan; Ren-jie Chen; Ying Zou (Environmental Science and Pollution Research, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Microtubule Stabilization Promotes Microcirculation Reconstruction After Spinal Cord Injury - Yang-Yang Duan; Yong Chai; Nai-Li Zhang; Dong-Mei Zhao; Cheng Yang (Journal of Molecular Neuroscience, 2021)
Spinal cord microcirculation plays an important role in maintaining the function of spinal cord neurons and other cells. Previous studies have largely focused on the ability of microtubule stabilization to inhibit the fibroblast migration and promote axon regeneration after spinal cord injury (SCI). However, the effect of microtubule stabilization treatment on microcirculation reconstruction after SCI remains unclear. By using immunofluorescence, we found that microtubule stabilization treatment improved microcirculation reconstruction via increasing the number of microvessels, pericytes, and the perfused microvessels after SCI. To clarify the underlying mechanisms, rat brain microvascular endothelial cells and pericytes were subjected to glucose oxygen deprivation. By using flow cytometry and western blotting, we found that microtubule stabilization treatment inhibited apoptosis and migration of endothelial cells and pericytes but promoted proliferation and survival of endothelial cells and pericytes through upregulated expression of vascular endothelial growth factor A (VEGFA), VEGF receptor 2, platelet-derived growth factor-B (PDGFB), PDGF receptor β, and angiopoietin-1 after SCI. Taken together, this study provides evidence for the mechanisms underlying the promotion of microcirculation reconstruction after SCI by microtubule stabilization treatment. Importantly, this study suggests the potential of microtubule stabilization as a therapeutic target to reduce microcirculation dysfunction after SCI in the clinic.

Genetic diversity analysis of Topmouth Culter (Culter alburnus) based on microsatellites and D-loop sequences - Ning Sun; Dong-Mei Zhu; Qing Li; Gui-Ying Wang; Jian Chen; Feifei Zheng; Pei Li; Yan-Hong Sun (Environmental Biology of Fishes, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

Report of epibenthic macrofauna found from Haima cold seeps and adjacent deep-sea habitats, South China Sea - Dong Dong; Xinzheng Li; Mei Yang; Lin Gong; Yang Li; Jixing Sui; Zhibin Gan; Qi Kou; Ning Xiao; Junlong Zhang (Marine Life Science & Technology, 2021)
This work reports on a preliminary taxonomic study of epibenthic macroinvertebrates collected or observed by underwater video at the Haima cold seeps and in adjacent deep-sea habitats, including a mud volcano field and Ganquan Plateau, during an expedition in the South China Sea by the Chinese-manned submersible Shenhai Yongshi in May 2018. A total of 41 species belonging to 6 phyla were identified, among which 34 species were collected from the Haima cold seeps. Mollusks and crustaceans that are specialized in reducing habitats were predominant in biotopes of the Haima cold seeps, whereas sponges and cold-water corals and their commensals were prominent in communities of the mud volcano field and the slopes of Ganquan Plateau. The distribution and faunal composition of each taxonomic group are discussed.

Julichrome derivatives and gliotoxin from a soil derived Streptomyces sp. - Tong Shen; Le-Mei Li; Ze-Yu Xu; Yong-Dong Wang; Wei-Dong Xie (Natural Product Research, 2021)

Spororrminone A and 2- epi -spororrminone A, two new chromones from an endolichenic fungus Sporormiella irregularis - Mei-Juan Huang; Yan-Jun Li; Jia Tang; Guo-Dong Chen; Dan Hu; Wei Xu; Liang-Dong Guo; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2020)

A new demethyl abietane diterpenoid from the roots of Tripterygium wilfordii - Peng Li; Shao-Xin Shen; Ling-Xue Liu; Jian-Hua Xu; Xin-Hua Ma; Dong-Mei Shi; Zhi-Qiang Zhang (Natural Product Research, 2020)

Efficient CRISPR/Cas9-mediated gene editing in Guangdong small-ear spotted pig cells using an optimized electrotransfection method - Yan-yan Wei; Qun-mei Zhan; Xiang-xing Zhu; Ai-fen Yan; Juan Feng; Lian Liu; Jian-hao Li; Dong-sheng Tang (Biotechnology Letters, 2020)

Deinococcus detaillensis sp. nov., isolated from humus soil in Antarctica - Kun Zhang; Jing Zhu; Shuai Li; Manik Prabhu Narsing Rao; Ning-Mei Li; Ang-Yang Guo; Zhao Jiang; Qi-Yong Tang; Yi Wan; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

The association between dioxins and steroid hormones in general adult males: a cross-sectional study in an e-waste region of China - Li Li Shi; Mei Qin Wang; Shoji F. Nakayama; Chau-Ren Jung; Yue Hua Wang; Jing Jian Dong; Chao Chen Ma; Teruhiko Kido; Xian Liang Sun; Hao Feng (Environmental Science and Pollution Research, 2020)

Analysis of Myoglobin Stability and Bacterial Community Diversity in Mutton Chop Rolls During Cold Preservation - Xue-Qi Zhang; Tao Jiang; Na Guo; Li Bai; Dong-Mei Zhao (Current Microbiology, 2020)

A new triterpenoid saponin from Pulsatilla cernua predicted by NMR-based mosaic method - An-Dong Wang; Ying Bao; Xia Wang; Mei-Chen Li; Xu-Hong Ren; Jian-Yu Liu; Yong-Nan Xu (Natural Product Research, 2020)

Field survey study on the difference in Cd accumulation capacity of rice and wheat in rice-wheat rotation area - Jiang-li Yang; Long Cang; Xia Wang; Hong-ting Xu; Dong-mei Zhou (Journal of Soils and Sediments, 2020)

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

Tillage practices improve rice yield and soil phosphorus fractions in two typical paddy soils - Waqas Ahmed; Muhammad Qaswar; Huang Jing; Dong Wenjun; Sun Geng; Liu Kailou; Meng Ying; Tang Ao; Sun Mei; Li Chao; Xu Yongmei; Sehrish Ali; et al. (Journal of Soils and Sediments, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Comparison between two kinds of natural pollen traps in tropical China: ants’ nests on tree branches versus surface soil - Zhi-Yong Zhang; Feng-Chun Yang; Dong-Mei Cheng; David K. Ferguson; Wan Hu; Yue-Zhuo Li; Cheng-Sen Li (Palynology, 2020)

Genome-Wide Association Study of Cerebral Microbleeds on MRI - Hong-Qi Li; Wen-Jie Cai; Xiao-He Hou; Mei Cui; Lan Tan; Jin-Tai Yu; Qiang Dong (Neurotoxicity Research, 2020)

Cytological, genetic, and proteomic analysis of a sesame (Sesamum indicum L.) mutant Siyl-1 with yellow–green leaf color - Tong-Mei Gao; Shuang-Ling Wei; Jing Chen; Yin Wu; Feng Li; Li-Bin Wei; Chun Li; Yan-Juan Zeng; Yuan Tian; Dong-Yong Wang; Hai-Yang Zhang (Genes & Genomics, 2020)
Background Both photosynthetic pigments and chloroplasts in plant leaf cells play an important role in deciding on the photosynthetic capacity and efficiency in plants. Systematical investigating the regulatory mechanism of chloroplast development and chlorophyll (Chl) content variation is necessary for clarifying the photosynthesis mechanism for crops. Objective This study aims to explore the critical regulatory mechanism of leaf color mutation in a yellow–green leaf sesame mutant Siyl - 1 . Methods We performed the genetic analysis of the yellow-green leaf color mutation using the F 2 population of the mutant Siyl - 1 . We compared the morphological structure of the chloroplasts, chlorophyll content of the three genotypes of the mutant F 2 progeny. We performed the two-dimensional gel electrophoresis (2-DE) and compared the protein expression variation between the mutant progeny and the wild type. Results Genetic analysis indicated that there were 3 phenotypes of the F 2 population of the mutant Siyl - 1 , i.e., YY type with light-yellow leaf color (lethal); Yy type with yellow-green leaf color, and yy type with normal green leaf color. The yellow-green mutation was controlled by an incompletely dominant nuclear gene, Siyl - 1 . Compared with the wild genotype, the chloroplast number and the morphological structure in YY and Yy mutant lines varied evidently. The chlorophyll content also significantly decreased ( P < 0.05 ). The 2-DE comparison showed that there were 98 differentially expressed proteins (DEPs) among YY, Yy, and yy lines. All the 98 DEPs were classified into 5 functional groups. Of which 82.7% DEPs proteins belonged to the photosynthesis and energy metabolism group. Conclusion The results revealed the genetic character of yellow-green leaf color mutant Siyl - 1 . 98 DEPs were found in YY and Yy mutant compared with the wild genotype. The regulation pathway related with the yellow leaf trait mutation in sesame was analyzed for the first time. The findings supplied the basic theoretical and gene basis for leaf color and chloroplast development mechanism in sesame.

The efflux pump inhibitor tetrandrine exhibits synergism with fluconazole or voriconazole against Candida parapsilosis - Ya-Jing Zhao; Wei-Da Liu; Yong-Nian Shen; Dong-Mei Li; Kun-Ju Zhu; Hong Zhang (Molecular Biology Reports, 2019)

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

Use of thermal imaging and Fourier transform infrared spectroscopy for the pre-symptomatic detection of cucumber downy mildew - Dong-Mei Wen; Mei-Xiang Chen; Li Zhao; Tao Ji; Ming Li; Xin-Ting Yang (European Journal of Plant Pathology, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Comprehensive genetic diagnosis of patients with Duchenne/Becker muscular dystrophy (DMD/BMD) and pathogenicity analysis of splice site variants in the DMD gene - Yan-mei Yang; Kai Yan; Bei Liu; Min Chen; Li-ya Wang; Ying-zhi Huang; Ye-qing Qian; Yi-xi Sun; Hong-ge Li; Min-yue Dong (Journal of Zhejiang University-SCIENCE B, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Biodiversity and antifouling activity of fungi associated with two soft corals from the South China Sea - Xiao-Yong Zhang; Hui-Li Hao; Stanley Chun Kwan Lau; Huai-You Wang; Yu Han; Li-Mei Dong; Ri-Ming Huang (Archives of Microbiology, 2019)

Effects of perinatal dioxin exposure on development of children: a 3-year follow-up study of China cohort - Zheng Wang; Jin Guo Hang; Hao Feng; Li Li Shi; Jing Jian Dong; Bin Shen; Ting Luo; Ren Mei Cai; Ling Jie Shen; Teruhiko Kido; Xian Liang Sun (Environmental Science and Pollution Research, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Identification and Functional Characterization of the DcF3’H Promoter from Dracaena cambodiana - Jiahong Zhu; Pan Chen; Dong Guo; Huiliang Li; Ying Wang; Haofu Dai; Wenli Mei; Shiqing Peng (Tropical Plant Biology, 2018)

8-isopentenyl isoflavone derivatives from the whole herb of Sphaerophysa salsula - Li-Jin Jiao; Wei-Dong Wang; Yan-Duo Tao; Yun Shao; Li-Juan Mei; Zeng-Gen Liu; Qi-Lan Wang; Jun Dang (Natural Product Research, 2018)

The release of cytochrome c and the regulation of the programmed cell death progress in the endosperm of winter wheat (Triticum aestivum L.) under waterlogging - Yuan-Hong Qi; Fang-Fang Mao; Zhu-Qing Zhou; Dong-Cheng Liu; Min-Yu; Xiang-Yi Deng; Ji-Wei Li; Fang-Zhu Mei (Protoplasma, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Synergistic effects and related bioactive mechanisms of Potentilla fruticosa Linn. leaves combined with green tea polyphenols studied with microbial test system (MTS) - Ze-Hua Liu; Zi-Wen Luo; Deng-Wu Li; Dong-Mei Wang; Xia Ji (Natural Product Research, 2018)

Repressible Transgenic Sterilization in Channel Catfish, Ictalurus punctatus, by Knockdown of Primordial Germ Cell Genes with Copper-Sensitive Constructs - Hanbo Li; Baofeng Su; Guyu Qin; Zhi Ye; Ahmed Elaswad; Ahmed Alsaqufi; Dayan A. Perera; Zhenkui Qin; Ramji Odin; Khoi Vo; David Drescher; Dalton Robinson; et al. (Marine Biotechnology, 2018)

Emerging role of semaphorin-3A in autoimmune diseases - Li-Na Liu; Xiao-Mei Li; Dong-Qing Ye; Hai-Feng Pan (Inflammopharmacology, 2018)

Synthesis, crystal structure, and antinociceptive effects of some new riluzole derivatives - Xiang-Long Wu; Liu Liu; You-Jia Li; Jie Luo; Dong-Wei Gai; Ting-Li Lu; Qi-Bing Mei (Medicinal Chemistry Research, 2018)

Identification, characterization and expression analysis of genes involved in steroidal saponin biosynthesis in Dracaena cambodiana - Jia-Hong Zhu; Hui-Liang Li; Dong Guo; Ying Wang; Hao-Fu Dai; Wen-Li Mei; Shi-Qing Peng (Journal of Plant Research, 2018)

Successful Treatment by Surgery of a Primary Cutaneous Mucormycosis Caused by Mucor irregularis - Guan-zhao Liang; Wen-qi Xu; Xiao-li Zheng; Huan Mei; Gui-xia Lv; Yong-nian Shen; Dong-mei Li; Wei-da Liu (Mycopathologia, 2018)

Knockdown of PRMT1 suppresses IL-1β-induced cartilage degradation and inflammatory responses in human chondrocytes through Gli1-mediated Hedgehog signaling pathway - Lei Xia; Hong-Xing Zhang; Mei-Li Xing; Yu-Ben Xu; Peng Li; Liang-Ku Huang; Jie Bai; Zhao Tian; Zan-Dong Zhao (Molecular and Cellular Biochemistry, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Toxicological effects of microcystin-LR on earthworm (Eisenia fetida) in soil - Hong-Fei Wen; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Lei Chen; Quan-Ying Cai; Hui Li; Ce-Hui Mo; Dong-Mei Zhou; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Serum Copeptin Predicts Severity and Recurrent Stroke in Ischemic Stroke Patients - Wan-Zhong Tang; Xiao-Bo Wang; Huan-Ting Li; Mei Dong; Xiang Ji (Neurotoxicity Research, 2017)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Development of a Semi-nested PCR-Based Method for Specific and Rapid Detection of Alternaria solani Causing Potato Early Blight in Soil - Qing Gu; Zhi-Hui Yang; Dong-Mei Zhao; Dai Zhang; Qian Wang; Li-Song Ma; Jie-Hua Zhu (Current Microbiology, 2017)

Modulatory role of L-carnitine against microcystin-LR-induced immunotoxicity and oxidative stress in common carp - Xiu-Mei Chen; Gui-Liang Guo; Li Sun; Qiu-Shi Yang; Gui-Qin Wang; Dong-Ming Zhang (Fish Physiology and Biochemistry, 2017)

Effect of different nitrogen forms on the toxicity of Zn in wheat seedling root: a modeling analysis - Yi-Min Wang; Peng Wang; Xiu-Zhen Hao; Dong-Mei Zhou; Ji-Zhou Li (Environmental Science and Pollution Research, 2017)

Cloning and Stress-Induced Expression Analysis of Calmodulin in the Antarctic Alga Chlamydomonas sp. ICE-L - Ying-ying He; Yi-bin Wang; Zhou Zheng; Fang-ming Liu; Mei-ling An; Xiao-dong He; Chang-feng Qu; Lu-lu Li; Jin-lai Miao (Current Microbiology, 2017)

Terrimonas suqianensis sp. nov., isolated from a tetrabromobisphenol A-contaminated soil - Qing Chen; Xiao-Xia Zang; Xing Hang; Jing Chen; Hong-Mei Wang; Shun-Peng Li; Jian-Dong Jiang; Kai Chen (Antonie van Leeuwenhoek, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

Two new xanthone epimers from the processed gamboge - Bang Dong; Yun-Feng Zheng; Hong-Mei Wen; Xin-Zhi Wang; Hai-Wei Xiong; Hao Wu; Wei Li (Natural Product Research, 2017)

The ferredoxin-dependent glutamate synthase (OsFd-GOGAT) participates in leaf senescence and the nitrogen remobilization in rice - Dong-Dong Zeng; Ran Qin; Mei Li; Md. Alamin; Xiao-Li Jin; Yu Liu; Chun-Hai Shi (Molecular Genetics and Genomics, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Control of the pollution of antibiotic resistance genes in soils by quorum sensing inhibition - Bai-Min Lai; Kun Zhang; Dong-Sheng Shen; Mei-Zhen Wang; Jia-Li Shentu; Na Li (Environmental Science and Pollution Research, 2017)

Attraction of Coffee Bean Weevil, Araecerus fasciculatus, to Volatiles from the Industrial Yeast Kluyveromyces lactis - Shuai Yang; Xiang-Dong Mei; Xiao-Fang Zhang; Yao-Fa Li; Dongmei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Vimentin is important in the neural differentiation of PC12 cells promoted by sialylation - Li Hui Wu; Xiao Ting Shao; Jun Xia Guo; Hui Sun; Qi Chen; Jing Pan; Qian Qian Cai; Yi Wei Dong; Zhong Yi Chen; Xiao Mei Yan; Min Peng; Nanbert Zhong; et al. (Glycoconjugate Journal, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

The prevalence and genotype distribution of rotavirus A infection among children with acute gastroenteritis in Kunming, China - Ziqin Dian; Mao Fan; Binghui Wang; Yue Feng; Hao Ji; Shuwei Dong; A-Mei Zhang; Li Liu; Hua Niu; Xueshan Xia (Archives of Virology, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Identification of novel polymorphic microsatellite loci in the endangered Chinese sucker (Myxocyprinus asiaticus) - NIAN XU; DONG-MEI XU; YAN-FU QUE; FANG SHI; MEI-HUA XIONG; KE SHAO; WEI-TAO LI; BIN ZHU; ZHONG YANG (Journal of Genetics, 2016)

A new flavonoid glycoside from Elsholtzia bodinieri - Jin-Dong Zhong; Yue Feng; Hong-Mei Li; Xue-Shan Xia; Rong-Tao Li (Natural Product Research, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Use of cardioselective β-blockers and overall death and cardiovascular outcomes in patients with COPD: a population-based cohort study - Yaa-Hui Dong; Chia-Hsuin Chang; Li-Chiu Wu; Mei-Shu Lai (European Journal of Clinical Pharmacology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Analysis of gene expression and histone modification between C4 and non-C4 homologous genes of PPDK and PCK in maize - Xiu-mei Dong; Yuan Li; Qing Chao; Jie Shen; Xiu-jie Gong; Biligen-gaowa Zhao; Bai-chen Wang (Photosynthesis Research, 2016)

Interaction between STAT3 gene polymorphisms and smoking on Crohn’s disease susceptibility: a case–control study in a Chinese Han population - Jun-hong Li; Ning Wu; Hong-mei Yang; Hong-bing Tang; Dong-ping Bao; Jun-min Ji (Inflammation Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Evaluating the fraction of electrically associated cations on surfaces of soil particles by extrapolation of strong-field Wien effect measurements in dilute suspensions - Ting-Ting Fan; Yu-Jun Wang; Cheng-Bao Li; Juan Gao; Dong-Mei Zhou; Shmulik P. Friedman (Journal of Soils and Sediments, 2016)

Thrombomodulin and High-Sensitive C-Reactive Protein Levels in Blood Correlate with the Development of Cerebral Infarction Among Asians - Yan Han; Shuai Wu; Qiang Hu; Jian-Qi Xiao; Dong-Mei Wei; Li-Li Liu; Ze-Zhi Li (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Cripto-1 modulates macrophage cytokine secretion and phagocytic activity via NF-κB signaling - Dong-mei Zhang; Yong-Li Bao; Chun-Lei Yu; Yi-meng Wang; Zhen-Bo Song (Immunologic Research, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Chemotherapeutic agent CPT-11 eliminates peritoneal resident macrophages by inducing apoptosis - Mei-Yun Huang; Hao Pan; Yi-Dan Liang; Hong-Xia Wei; Li-Hui Xu; Qing-Bing Zha; Xian-Hui He; Dong-Yun Ouyang (Apoptosis, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Complete genome sequence of a distinct calla lily chlorotic spot virus isolated in mainland China - Ye Xu; Si-bo Wang; Yong-zhong Li; Hong-zheng Tao; Ya-ning Huang; Bao-wei Wu; Yu-mei Dong; John Hu; Ya-ting Liu (Archives of Virology, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Genome-wide identification of allele-specific expression in response to Streptococcus suis 2 infection in two differentially susceptible pig breeds - Huayu Wu; Uma Gaur; Supamit Mekchay; Xianwen Peng; Lianghua Li; Hua Sun; Zhongxu Song; Binke Dong; Mingbo Li; Klaus Wimmers; Siriluck Ponsuksili; Kui Li; et al. (Journal of Applied Genetics, 2015)

Detection of Vulnerable Atherosclerotic Plaques in Experimental Atherosclerosis with the USPIO-Enhanced MRI - Chun-mei Qi; Lili Du; Wei-heng Wu; Dong-ye Li; Ji Hao; Lei Gong; Liangrong Deng; Tao Zhang; Chao Zhang; Yu Zhang (Cell Biochemistry and Biophysics, 2015)

Major and trace elements of abyssal peridotites: evidence for melt refertilization beneath the ultraslow-spreading Southwest Indian Ridge (53° E segment) - Ling Chen; Feng-You Chu; Ji-Hao Zhu; Yan-Hui Dong; Xing Yu; Zheng-Gang Li; Li-Mei Tang (International Geology Review, 2015)

Behavior, metabolism and swimming physiology in juvenile Spinibarbus sinensis exposed to PFOS under different temperatures - Ji-Gang Xia; Li-Juan Nie; Xia-Mei Mi; Wei-Zhen Wang; Yi-Jie Ma; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Effect from low-level exposure of oxytetracycline on abundance of tetracycline resistance genes in arable soils - Jia-li Shentu; Kun Zhang; Dong-sheng Shen; Mei-zhen Wang; Hua-jun Feng (Environmental Science and Pollution Research, 2015)

Variable-order rotated staggered-grid method for elastic-wave forward modeling - Wei-Zhong Wang; Tian-Yue Hu; Xue-Mei Lu; Zhen Qin; Yan-Dong Li; Yan Zhang (Applied Geophysics, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Two novel CAII mutations causing carbonic anhydrase II deficiency syndrome in two unrelated Chinese families - Qianqian Pang; Xuan Qi; Yan Jiang; Ou Wang; Mei Li; Xiaoping Xing; Jin Dong; Weibo Xia (Metabolic Brain Disease, 2015)

Actinomadura amylolytica sp. nov. and Actinomadura cellulosilytica sp. nov., isolated from geothermally heated soil - Jian-Yu Jiao; Lan Liu; En-Min Zhou; Da-Qiao Wei; Hong Ming; Wen-Dong Xian; Chang-Guo Yuan; Jing-Mei Zhong; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Impacts of anthropogenic activities on the Changjiang (Yangtze) estuarine ecosystem (1998–2012) - Dong Chen; Zhijun Dai; Ren Xu; Daoji Li; Xuefei Mei (Acta Oceanologica Sinica, 2015)

The effects of land use and landscape position on labile organic carbon and carbon management index in red soil hilly region, southern China - Zhong-wu Li; Xiao-dong Nie; Xiao-lin Chen; Yin-mei Lu; Wei-guo Jiang; Guang-ming Zeng (Journal of Mountain Science, 2015)

Molecular Cloning and Characterization of a Short-Chain Dehydrogenase Showing Activity with Volatile Compounds Isolated from Camellia sinensis - Ying Zhou; Ling Zhang; Jiadong Gui; Fang Dong; Sihua Cheng; Xin Mei; Linyun Zhang; Yongqing Li; Xinguo Su; Susanne Baldermann; Naoharu Watanabe; Ziyin Yang (Plant Molecular Biology Reporter, 2015)

Yangtze finless porpoises along the main channel of Poyang Lake, China: Implications for conservation - Lijun Dong; Ding Wang; Kexiong Wang; Songhai li; Zhigang Mei; Shiyong Wang; Tomonari Akamatsu; Satoko Kimura (Marine Mammal Science, 2015)
Poyang Lake is the largest freshwater lake in China and flows into the Yangtze River. It is a traditional habitat for the endangered Yangtze finless porpoise, which has not been well investigated. To reveal the distribution of the porpoise in Poyang Lake, 12 passive acoustic surveys were conducted along 123 km of the main channel of the lake during different seasons (spring transition season, wet season, autumn transition season, and dry season) from 2008 to 2012. We counted the number of phonating porpoises encountered and calculated the detection rate (encountered individuals detected per kilometer). The median porpoise detection rates ranged from 0 to 0.65 individuals per kilometer during the different surveys. The highest median detection rate of 0.50 was detected in the autumn transition season. The seasonal shrinking of the lake during the dry season may cause a concentration of porpoises in the narrow channels and a high incidence of collisions with cargo ships and fishing boats. Conservation actions should be focused on the main channel of the lake during the dry and transition seasons. In addition, the expansion of the existing reserve to include areas with high porpoise detection rates is necessary.

Study on the Diversity of Bacteroides and Clostridium in Patients with Primary Gout - Shi-Chao Xing; Dong-Mei Meng; Ying Chen; Gang Jiang; Xi-Shuang Liu; Na Li; Yao-Yao Yan; Chang-Gui Li (Cell Biochemistry and Biophysics, 2015)

The decreased frequency of SIGIRR-positive CD4+ T cells in peripheral blood of patients with SLE and its correlation with disease activity - Dao-Yang Wang; Chao Su; Gui-Mei Chen; Hai-Feng Pan; Feng-Mei Wang; Gui-Ling Liu; Li Hao; De-Guang Wang; Dong-Qing Ye (Molecular Biology Reports, 2015)

Chemical modification, characterization and bioactivity of a released exopolysaccharide (r-EPS1) from Lactobacillus plantarum 70810 - Kun Wang; Wei Li; Xin Rui; Teng Li; Xiaohong Chen; Mei Jiang; Mingsheng Dong (Glycoconjugate Journal, 2015)

A modified genetic model for the Huangshandong magmatic sulfide deposit in the Central Asian Orogenic Belt, Xinjiang, western China - Ya-Jing Mao; Ke-Zhang Qin; Chusi Li; Dong-Mei Tang (Mineralium Deposita, 2015)

Drug-Induced Modulation of T Lymphocytes as a Potential Mechanism of Susceptibility to Infections in Patients with Multiple Myeloma During Bortezomib Therapy - Juan Li; Ying Li; Beihui Huang; Dong Zheng; Mei Chen; Zhenhai Zhou (Cell Biochemistry and Biophysics, 2015)
Bortezomib is effective in the therapy of multiple myeloma (MM), but causes infections that are different from those associated with conventional chemotherapy. It is important to identify the risk factors that facilitate infections associated with bortezomib therapy. In the present report, we sought to (1) define the features of the infections associated with this therapy and (2) identify the immune mechanisms responsible for the observed susceptibility to these infections. We first retrospectively analyzed the clinical data of 143 patients who had received bortezomib therapy for MM. We then prospectively assessed the modulation of T lymphocyte status during this therapy, and evaluated potential relationships between infections and T lymphocyte changes. The infection rates peaked during the first cycle of bortezomib therapy (47.6 %) in patients with MM ( p < 0.05 vs. subsequent cycles). Bortezomib therapy was associated with higher incidence rates of viral and fungal infections (15.8 %, p < 0.05 vs. conventional chemotherapy). In addition, patients with the IgG immunophenotype showed higher bacterial and viral infection rates (respectively, p = 0.008 and 0.009). The T lymphocyte numbers significantly decreased after bortezomib therapy ( p < 0.05), and the same was true for the Th1/Th2 ratio ( p < 0.01). Patients with MM who have decreased lymphocyte counts, while on bortezomib therapy are more likely to develop bacterial or viral infections. In addition, an imbalance in T lymphocyte subsets is also associated with bacterial or viral infections in these patients.

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Analysis on the Clinical Features of 507 HDV-Infected Patients - Xiao-hong Gu; Zhuo Chen; Ruo-yi Dai; Min-li Zhang; Hou-mei Tang; Lan-bo Chen; Bo Dong (Cell Biochemistry and Biophysics, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Integration of metal chemical forms and subcellular partitioning to understand metal toxicity in two lettuce (Lactuca sativa L.) cultivars - Cheng-Cheng Li; Fei Dang; Long Cang; Chui-Fan Zhou; Dong-Mei Zhou (Plant and Soil, 2014)

Deciphering the molecular responses to methanol-enhanced photosynthesis and stomatal conductance in broad bean - Yan Zhao; Zhi-Dong Zeng; Chuan-Jiao Qi; Xue-Song Yu; Chuan-Long Guo; Qi Chen; Li-Mei Chen (Acta Physiologiae Plantarum, 2014)

Shinjulactone O, a new quassinoid from the root bark of Ailanthus altissima - Xiao-Lin Yang; Yong-Liang Yuan; Dong-Mei Zhang; Fei Li; Wen-Cai Ye (Natural Product Research, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Interaction network analysis revealed biomarkers in myocardial infarction - Tong Zhang; Li-Li Zhao; Zhuo-Ran Zhang; Pei-De Fu; Zhen-Dong Su; Li-Chun Qi; Xue-Qi Li; Yu-Mei Dong (Molecular Biology Reports, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

The Analysis of the Impact of Land-Use Changes on Flood Exposure of Wuhan in Yangtze River Basin, China - Jie Liu; Shao-yu Wang; Dong-mei Li (Water Resources Management, 2014)

Over-expression of heat shock factor gene (AtHsfA1d) from Arabidopsis thaliana confers formaldehyde tolerance in tobacco - Hong-Juan Nian; Dao-Jun Zhang; Zhi-Dong Zeng; Jin-Ping Yan; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Differences in Gene Expression and Regulation during Ontogenetic Phase Change in Apple Seedlings - Yan Gao; Feng Qiu Yang; Xin Cao; Chun Min Li; Yi Wang; Yong Bo Zhao; Guang Juan Zeng; Dong Mei Chen; Zhen Hai Han; Xin Zhong Zhang (Plant Molecular Biology Reporter, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

The novel coding region SNPs of PPARGC1A gene and their associations with growth traits in Chinese native cattle - Mijie Li; Mei Liu; Dong Liu; Xianyong Lan; Chuzhao Lei; Hong Chen (Molecular Biology Reports, 2014)

Dishevelled-1 (Dvl-1) Protein: a Potential Participant of Oxidative Stress Induced by Selenium Deficiency - Han-dong Zhao; Mei-na Sun; Meng-di Li; Feng-lan Li; Hui Li (Biological Trace Element Research, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Shotgun Analysis of the Secretome of Fusarium graminearum - Xian-Ling Ji; Mei Yan; Zai-Dong Yang; An-Fei Li; Ling-Rang Kong (Indian Journal of Microbiology, 2013)

ROCK is Involved in Vimentin Phosphorylation and Rearrangement Induced by Dengue Virus - Shun Lei; Yan-Ping Tian; Wei-Dong Xiao; Shu Li; Xian-Cai Rao; Jun-Lei Zhang; Jie Yang; Xiao-Mei Hu; Wei Chen (Cell Biochemistry and Biophysics, 2013)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Full-length sequence analysis of hepatitis E virus isolates: showing potential determinants of virus genotype and identity - Dong Yang; Mei Jiang; Min Jin; Zhigang Qiu; Weihong Cui; Zhiqiang Shen; Bo Li; Lianfeng Gong; Zhaoli Chen; Xinwei Wang; Jun-Wen Li (Virus Genes, 2013)

Tricycloalternarene derivatives from endophytic fungus Alternaria tenuissima SY-P-07 - Dong-Mei Li; Yu-Hong Zhang; Hai-Xia Ji; Xin Wu; Yue-Hu Pei; Jiao Bai (Natural Product Research, 2013)

Vascular endothelial growth factor (VEGF) gene polymorphisms and risk of head and neck cancer: a meta-analysis involving 2,444 individuals - Wei-Dong Leng; Mei-Ni He; Qi-Lin Chen; Heng Gong; Li Zhang; Xian-Tao Zeng (Molecular Biology Reports, 2013)

The effects of biotic and abiotic factors on the spatial heterogeneity of alpine grassland vegetation at a small scale on the Qinghai–Tibet Plateau (QTP), China - Lu Wen; Shi Kui Dong; Yuan Yuan Li; Ruth Sherman; Jian Jun Shi; De Mei Liu; Yan Long Wang; Yu Shou Ma; Lei Zhu (Environmental Monitoring and Assessment, 2013)

A novel role of ribonuclease inhibitor in regulation of epithelial-to-mesenchymal transition and ILK signaling pathway in bladder cancer cells - Xue Yao; Dan Li; Dong-mei Xiong; Lin Li; Rong Jiang; Jun-xia Chen (Cell and Tissue Research, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

HIF-1α up-regulates NDRG1 expression through binding to NDRG1 promoter, leading to proliferation of lung cancer A549 cells - Qiang Wang; Li-Hong Li; Guo-Dong Gao; Gang Wang; Liang Qu; Jin-Ge Li; Chun-Mei Wang (Molecular Biology Reports, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Characterization of acetylcholinesterase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Ying Du; Xiao-Qian Chai; Yoshiyuki Murata (Fisheries Science, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Exploring the effect of organic matter on the interactions between mineral particles and cations with Wien effect measurements - Yu-Jun Wang; Ling-Xiang Wang; Cheng-Bao Li; You-Bin Si; Dong-Mei Zhou (Journal of Soils and Sediments, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Involvement of antioxidant defense system in chill hardening-induced chilling tolerance in Jatropha curcas seedlings - Ping-Xing Ao; Zhong-Guang Li; Dong-Mei Fan; Ming Gong (Acta Physiologiae Plantarum, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Novel SNPs in the bovine Transmembrane protein 18 gene, their linkage and their associations with growth traits in Nanyang cattle - Wei Ma; Yun Ma; Dong Liu; Yuan Gao; Xiao-mei Sun; Ai-min Li; Chun-lei Zhang; Hong Chen (Genes & Genomics, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

Pretreatment with anti-flagellin serum delays acute lung injury in rats with sepsis - Ming-Dong Hu; Yu Yang; Chang-Xi Zhou; Qi Li; Wang Yi; Gui-Sheng Qian; Mei Mao; Jian-Cheng Xu (Inflammation Research, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

A ground spectral model for estimating biomass at the peak of the growing season in Hulunbeier grassland, Inner Mongolia, China - Ji-Xi Gao; Yan-Mei Chen; Shi-Hai Lü; Chao-Yang Feng; Xue-Li Chang; Sheng-Xing Ye; Ji-Dong Liu (International Journal of Remote Sensing, 2012)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

Cloning and expression of the two new variants of Nav1.5/SCN5A in rat brain - Cheng-Tao Ren; Dong-Mei Li; Shao-Wu Ou; Yun-Jie Wang; Yi Lin; Zhi-Hong Zong; Masaki Kameyama; Asako Kameyama (Molecular and Cellular Biochemistry, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Identification of markers linked to major gene loci involved in determination of fruit shape index of apples (Malus domestica) - Huan Huan Sun; Yong Bo Zhao; Chun Min Li; Dong Mei Chen; Yi Wang; Xin Zhong Zhang; Zhen Hai Han (Euphytica, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Triterpenoids with neurotrophic activity from Ganoderma lucidum - Xiao-Qi Zhang; Fanny C.F. Ip; Dong-Mei Zhang; Li-Xin Chen; Wei Zhang; Yao-Lan Li; Nancy Y. Ip; Wen-Cai Ye (Natural Product Research, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

QTL mapping of sheath blight resistance in a deep-water rice cultivar - Dong Fu; Liang Chen; Guohui Yu; Yi Liu; Qiaojun Lou; Hanwei Mei; Liang Xiong; Mingshou Li; Xiaoyan Xu; Lijun Luo (Euphytica, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Maslinic acid induces apoptosis in salivary gland adenoid cystic carcinoma cells by Ca2+-evoked p38 signaling pathway - Dong-Mei Wu; Dan Zhao; De-Zhi Li; Dong-Yang Xu; Wen-Feng Chu; Xiao-Feng Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Isolation of a LEAFY homolog from Populus tomentosa: expression of PtLFY in P. tomentosa floral buds and PtLFY-IR-mediated gene silencing in tobacco (Nicotiana tabacum) - Xin-Min An; Dong-Mei Wang; Ze-Liang Wang; Bo Li; Wen-Hao Bo; Guan-Lin Cao; Zhi-Yi Zhang (Plant Cell Reports, 2011)

Evaluating mechanisms for plant-ion (Ca2+, Cu2+, Cd2+ or Ni2+) interactions and their effectiveness on rhizotoxicity - Peng Wang; Dong-Mei Zhou; Willie J. G. M. Peijnenburg; Lian-Zhen Li; Nanyan Weng (Plant and Soil, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Synthesis and evaluation of antiinflammatory activity of substituted chalcone derivatives - Xue-Wu Zhang; Dong-Hai Zhao; Ying-Chun Quan; Liang-Peng Sun; Xiu-Mei Yin; Li-Ping Guan (Medicinal Chemistry Research, 2010)

Molecular Cloning and Characterization of a Chitinase-Homologous Gene from Mikania micrantha Infected by Cuscuta campestris - Dong-Mei Li; Christian Staehelin; Wen-Tian Wang; Shao-Lin Peng (Plant Molecular Biology Reporter, 2010)

RA induces the neural-like cells generated from epigenetic modified NIH/3T3 cells - Xi-Mei Zhang; Qiu-Ming Li; Dong-Ju Su; Ning Wang; Zhi-Yan Shan; Lian-Hong Jin; Lei Lei (Molecular Biology Reports, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Responses of two rice cultivars differing in seedling-stage nitrogen use efficiency to growth under low-nitrogen conditions - Wei Ming Shi; Wei Feng Xu; Su Mei Li; Xue Qiang Zhao; Gang Qiang Dong (Plant and Soil, 2010)

Effect of high glucose concentration on VEGF and PEDF expression in cultured retinal Müller cells - Hua Mu; Xiao-Mei Zhang; Jian-Ju Liu; Li Dong; Zhuo-Lei Feng (Molecular Biology Reports, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Effects of Elevated Atmospheric CO2 and O3 on Hill Activity and Ca2+/Mg2+-ATPase Activity of Pinus tabulaeformis Carr. - Tian Hong Zhao; Dan Guo; Yan Wang; Mei Yu Wang; Dong Yan Jin; Jun Li Wang; Xing Yuan He (Bulletin of Environmental Contamination and Toxicology, 2009)

Serum Zinc, Copper, and Zinc/Copper in Healthy Residents of Jinan - Hong-qun Zhang; Ning Li; Zheng Zhang; Shan Gao; Hong-yin Yin; Dong-mei Guo; Xibao Gao (Biological Trace Element Research, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Oxidative damage increased in presenilin1/presenilin2 conditional double knockout mice - Dong-Li Zhang; Yi-Qun Chen; Xu Jiang; Ting-Ting Ji; Bing Mei (Neuroscience Bulletin, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Coleus blumei viroid 6: a new tentative member of the genus Coleviroid derived from natural genome shuffling - Wan-Ying Hou; Shi-Fang Li; Zu-Jian Wu; Dong-Mei Jiang; Teruo Sano (Archives of Virology, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Distribution and Accumulation of Copper and Cadmium in Soil–Rice System as Affected by Soil Amendments - Ping Li; Xing-xiang Wang; Tao-lin Zhang; Dong-mei Zhou; Yuan-qiu He (Water, Air, & Soil Pollution, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Simultaneous detection of human enterovirus 71 and coxsackievirus A16 in clinical specimens by multiplex real-time PCR with an internal amplification control - Xing-Long Xiao; Ya-Qing He; Yi-Gang Yu; Hong Yang; Gu Chen; Hui-Fang Li; Jing-Wei Zhang; Dong-Mei Liu; Xiao-Feng Li; Xiao-Quan Yang; Hui Wu (Archives of Virology, 2009)

Death and proliferation of chondrocytes in the degraded mandibular condylar cartilage of rats induced by experimentally created disordered occlusion - Kai Jiao; Mei-Qing Wang; Li-Na Niu; Juan Dai; Shi-Bin Yu; Xiao-Dong Liu; Guo-Wei Wang (Apoptosis, 2009)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

Binding of Ni2+ to a histidine- and glutamine-rich protein, Hpn-like - Yi-Bo Zeng; Dong-Mei Zhang; Hongyan Li; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2008)

Effect of Major Cations and pH on the Acute Toxicity of Cadmium to the Earthworm Eisenia fetida: Implications for the Biotic Ligand Model Approach - Lian-Zhen Li; Dong-Mei Zhou; Xiao-San Luo; Peng Wang; Quan-Ying Wang (Archives of Environmental Contamination and Toxicology, 2008)

A novel fibrinolytic enzyme from Cordyceps militaris, a Chinese traditional medicinal mushroom - Li Cui; Ming Sheng Dong; Xiao Hong Chen; Mei Jiang; Xin Lv; Guijun Yan (World Journal of Microbiology and Biotechnology, 2008)

RNA interference mediated silencing of α-synuclein in MN9D cells and its effects on cell viability - Dong-Mei Liu; Ling Jin; Hao Wang; Huan-Ying Zhao; Chun-Li Zhao; Hui Yang (Neuroscience Bulletin, 2008)

Origin of the Tongshankou porphyry–skarn Cu–Mo deposit, eastern Yangtze craton, Eastern China: geochronological, geochemical, and Sr–Nd–Hf isotopic constraints - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Paulo Vasconcelos; Chang-Qian Ma; Xiao-Dong Deng; Zorano Sérgio de Souza; Yong-Xin Zhao; Gang Wu (Mineralium Deposita, 2008)

Cloning and characterization of chicken SPATA4 gene and analysis of its specific expression - Ming-Chao Xie; Chao Ai; Xiu-Mei Jin; Shang-Feng Liu; Shi-Xin Tao; Zan-Dong Li; Zhao Wang (Molecular and Cellular Biochemistry, 2007)

Local Delivery of Indomethacin to Arthritis-Bearing Rats through Polymeric Micelles Based on Amphiphilic Polyphosphazenes - Jian Xiang Zhang; Mei Qiu Yan; Xiao Hui Li; Li Yan Qiu; Xiao Dong Li; Xiao Jing Li; Yi Jin; Kang Jie Zhu (Pharmaceutical Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Study on Metsulfuron-Methyl Degradation in Simulated Wheat (Triticum Asetivum L.) Rhizospheric Soil with Penicillium sp. Inoculation - Yong Hua He; Dong Sheng Shen; Li Fang Hu; Yin Mei Zhu (Water, Air, & Soil Pollution, 2007)

Dynamics of Typical Agricultural Landscape and its Relationship With Water Resource in Inland Shiyang River Watershed, Gansu Province, Northwest China - Li Xiao-Yu; Xiao Du-Ning; He Xing-Yuan; Chen Wei; Song Dong-Mei (Environmental Monitoring and Assessment, 2006)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

The Synthesis and Characterization of a Helical Miniature Protein Mimicking the OGT Active Domain - Hua-Dong Liu; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2006)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Fed-batch fermentation of Lactobacillus lactis for hyper-production of l-lactic acid - Dong-Mei Bai; Qiang Wei; Zhi-Hui Yan; Xue-Ming Zhao; Xin-Gang Li; Shi-Min Xu (Biotechnology Letters, 2003)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

The types of lake in Songnen Plain and their regional character - Jin-fu Lu; Dong-mei Jie; Zhi-min Li; Xue-tian Leng (Chinese Geographical Science, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)